Resin composition
Patent Information
- Application Number
- CN202580024011.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-29
- Filing Date
- 2025-03-27
- Publication Date
- 2026-11-03
AI Technical Summary
Existing technologies struggle to simultaneously achieve low dielectric loss tangent and suppress warping after curing in large-scale semiconductor packaging, while reliability is reduced during reflow soldering.
A resin composition is formed by combining a compound with a weight average molecular weight between 5,000 and 300,000 and terminally possessing a free radical polymerizable group, along with an inorganic filler and a compound with a molecular weight of less than 5,000. The composition preferably contains an imide backbone and specific structural units, along with components such as a polymerization initiator and a polymer resin.
It achieves low dielectric loss tangent, suppresses warping after curing, improves reflow solderability, and ensures the reliability of the cured product.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to resin compositions. Furthermore, it relates to cured resin compositions, resin sheets, circuit boards, and semiconductor devices. Background Technology
[0002] In insulating materials such as sealing materials for semiconductor chip packages and interlayer insulating materials for circuit boards, the necessity of low dielectric loss tangent is increasing for next-generation high-speed communications. Furthermore, in wafer-level packaging (WLP) and panel-level packaging (PLP), with the increasing demand for larger substrates, reducing warpage in the overall package structure is becoming more important.
[0003] In the past, excellent dielectric properties were ensured by mixing large amounts of inorganic fillers or stress relaxants, while low warpage was achieved through low thermal expansion and stress relaxation capabilities (e.g., Patent Document 1).
[0004] Existing technical documents Patent documents Patent document 1: Japanese Patent Application Publication No. 2018-168217. Summary of the Invention
[0005] The problem the invention aims to solve On the other hand, if further low warpage is required due to the demand for larger sizes, more stress relaxants need to be added, but it is known that they have an inverse relationship with low dielectric loss tangent. In addition, in cured products exhibiting low dielectric loss tangent, expansion sometimes occurs between the cured product and the wiring (conductor layer) when supplied for reflow soldering, reducing reliability.
[0006] The present invention was made in view of the above circumstances, and its object is to provide a resin composition that achieves a low dielectric loss tangent, suppresses warping after curing, and has excellent reflow solderability; a cured resin composition; a resin sheet comprising the resin composition; a circuit board comprising the cured resin composition; and a semiconductor device comprising the circuit board.
[0007] Methods for solving problems The inventors conducted in-depth research to solve the aforementioned problems. As a result, the inventors discovered that the aforementioned problems could be solved by using the following resin composition, thereby completing the present invention, which comprises: (A) a compound having free radical polymerizable groups at the ends, a weight-average molecular weight (Mw) of more than 5,000 and less than 300,000, and a tensile modulus of elasticity of less than 1 GPa as measured at 25°C according to JIS K7161; (B) an inorganic filler material; and (C) a compound having free radical polymerizable groups and a weight-average molecular weight (Mw) of less than 5,000.
[0008] That is, the present invention includes the following technical solutions.
[0009] <1> A resin composition comprising: (A) a compound having a terminal free radical polymerizable group, a weight-average molecular weight (Mw) of more than 5,000 and less than 300,000, and a tensile modulus of elasticity of less than 1 GPa as determined by JIS K7161 at 25°C; (B) an inorganic filler; and (C) a compound having a free radical polymerizable group and a weight-average molecular weight (Mw) of less than 5,000.
[0010] <2> according to <1> The resin composition wherein component (A) comprises an imide backbone.
[0011] <3> according to <1> or <2> The resin composition wherein component (A) comprises an imide backbone in the main chain.
[0012] <4> according to <1> ~ <3> The resin composition of any one of the following is wherein component (A) comprises the structure shown in formula (A-1).
[0013] [Chemistry 1] (In formula (A-1), R) A1 * indicates a tetravalent group obtained by removing the anhydride group from a tetracarboxylic dianhydride; * indicates a linking bond.
[0014] <5> according to <4> The resin composition wherein (A) component combination comprises the structure shown in the aforementioned formula (A-1) and the structure shown in the following formula (A-3).
[0015] [Chemistry 2] (In formula (A-3), R) A3 * indicates a divalent group obtained by removing two hydroxyl groups from a polyol compound having two or more hydroxyl groups in one molecule; * indicates a linking bond.
[0016] <6> according to <1> ~ <5> The resin composition according to any one of the following, wherein the content of component (B) is 50% by mass or more relative to 100% by mass of the non-volatile components of the resin composition.
[0017] <7> according to <1> ~ <6> The resin composition according to any one of the following, wherein component (A) comprises one or more structural units selected from polyolefin structural units, polycarbonate structural units, polyether structural units, polyester structural units, poly(meth)acrylic structural units and polysiloxane structural units.
[0018] <8> according to <1> ~ <7> The resin composition of any one of the following, wherein component (A) comprises a polyolefin structural unit.
[0019] <9> according to <1> ~ <8> The resin composition of any one of the following, wherein component (C) comprises a maleimide-based free radical polymerizable compound.
[0020] <10> according to <1> ~ <9> The resin composition according to any one of the following, wherein the content of component (A) is 0.1% by mass or more and 30% by mass or less relative to 100% by mass of the non-volatile components of the resin composition.
[0021] <11> according to <1> ~ <10> The resin composition according to any one of the following, wherein the content of component (C) is 5% by mass or more and 40% by mass or less relative to 100% by mass of the non-volatile components of the resin composition.
[0022] <12> according to <1> ~ <11> The resin composition according to any one of the following, wherein the mass ratio of component (A) to component (C) (content of component (A)) / (content of component (C)) is 0.01 or more and 1.5 or less.
[0023] <13> according to <1> ~ <12> The resin composition described in any one of the following examples further comprises (D) a polymerization initiator.
[0024] <14> according to <1> ~ <13> The resin composition described in any one of the following statements further comprises (E) a polymeric resin.
[0025] <15> according to <1> ~ <14> The resin composition described in any one of the above statements is used to form an insulating layer on a circuit board.
[0026] <16> Solidified material, which is <1> ~ <15> The cured product of the resin composition described in any one of the above statements.
[0027] <17> A resin sheet comprising a support and a resin composition layer formed on the support. The resin composition layer contains <1> ~ <15> The resin composition described in any one of the following statements.
[0028] <18> Circuit board, which includes <1> ~ <15> The cured product of the resin composition described in any one of the above statements.
[0029] <19> Semiconductor device, comprising <18> The circuit board mentioned above.
[0030] Invention Effects <Explanation of Terms> In this specification, the term "non-volatile component" in relation to the resin composition refers to the component constituting the resin composition other than the solvent described later. Furthermore, the term "resin component" in relation to the resin composition in this specification refers to the component constituting the non-volatile component of the resin composition other than the inorganic filler.
[0031] According to the present invention, a resin composition that achieves a low dielectric loss tangent, suppresses warping after curing, and has excellent reflow solderability can be provided; a cured resin composition; a resin sheet comprising the resin composition; a circuit board comprising the cured resin composition; and a semiconductor device comprising the circuit board. Detailed Implementation
[0032] Hereinafter, embodiments and examples of the present invention will be described in detail. However, the present invention is not limited to the embodiments and examples described below, and can be implemented in any way without departing from the scope of the claims and their equivalents.
[0033] [Resin Composition] The resin composition of the present invention is characterized by comprising: (A) a compound having a terminal free radical polymerizable group, a weight-average molecular weight (Mw) of more than 5,000 and less than 300,000, and a tensile modulus of elasticity of less than 1 GPa as measured at 25°C according to JIS K7161; (B) an inorganic filler; and (C) a compound having a terminal free radical polymerizable group and a weight-average molecular weight (Mw) of less than 5,000. In the following description, "(A) a compound having a terminal free radical polymerizable group, a weight-average molecular weight (Mw) of more than 5,000 and less than 300,000, and a tensile modulus of elasticity of less than 1 GPa as measured at 25°C according to JIS K7161" is sometimes referred to as "(A) a high molecular weight, low elasticity compound having a terminal free radical polymerizable group". In addition, sometimes “(C) a compound having a free radical polymerizable group and a weight-average molecular weight (Mw) of less than 5,000” is referred to as “(C) a compound having a free radical polymerizable group”.
[0034] The resin composition of the present invention may further include optional components in combination with components (A) to (C). Examples of optional components include, for example, (D) polymerization initiator, (E) polymer resin, (F) optional additive, and (G) solvent. Hereinafter, each component included in the resin composition will be described in detail.
[0035] <(A) High molecular weight, low elasticity compounds with terminal free radical polymerizable groups (compounds with terminal free radical polymerizable groups, weight-average molecular weight (Mw) exceeding 5,000 and below 300,000, and tensile modulus of elasticity below 1 GPa as determined by JIS K7161 at 25°C)> In the resin composition of the present invention, component (A) comprises a high molecular weight, low elasticity compound having a free radical polymerizable group at its end. The weight-average molecular weight (Mw) of component (A) is greater than 5,000 and less than 300,000. Furthermore, the tensile modulus of elasticity of component (A), measured at 25°C according to JIS K7161, is less than 1 GPa. In the resin composition of the present invention, component (A) may be used alone or in combination of two or more.
[0036] As described above, the weight-average molecular weight (Mw) of component (A) is greater than 5,000 and less than 300,000. The lower limit of the weight-average molecular weight (Mw) of component (A) is preferably 6,000 or more, more preferably 8,000 or more, and even more preferably 10,000 or more. The upper limit of this weight-average molecular weight is preferably 250,000 or less, more preferably 200,000 or less, even more preferably 150,000 or less, and even more preferably 100,000 or less, 80,000 or less, 60,000 or less, 50,000 or less, or 40,000 or less. The weight-average molecular weight of the high molecular weight-low elasticity compound (A) having a free radical polymerizable group at the end can be determined by gel permeation chromatography (GPC) in the form of a polystyrene equivalent.
[0037] Furthermore, as described above, in component (A), the tensile modulus of elasticity measured at 25°C according to JIS K7161 is 1 GPa or less. This tensile modulus of elasticity is preferably 0.5 GPa or less, more preferably 0.1 GPa or less, and even more preferably 0.05 GPa or less. There is no particular limitation on the lower limit of this tensile modulus of elasticity; it can be set to 0.01 MPa, etc. The method for determining the tensile modulus of elasticity of component (A) can be the method described later in <Synthesis Example 1: Synthesis of Elastomer A1>.
[0038] Component (A) has a free radical polymerizable group at its end. Examples of free radical polymerizable groups at the end of component (A) include vinyl, allyl, vinylphenyl, maleimide, and (meth)acryloyl. When component (A) contains two or more free radical polymerizable groups, these two or more free radical polymerizable groups may be the same or different. From the viewpoint that a cured product with a lower dielectric loss tangent, further suppression of warpage after curing, and better reflow soldering resistance can be achieved when combined with the inorganic filler material (B) and the compound having a free radical polymerizable group (C), and a resin composition layer with excellent appearance can be achieved, the free radical polymerizable group at the end of component (A) is preferably (meth)acryloyl.
[0039] From the viewpoint of achieving a cured product with lower dielectric loss tangent, further suppression of warpage after curing, and superior reflow soldering resistance by combining (B) inorganic filler material and (C) compounds with free radical polymerizable groups, component (A) preferably contains an imide skeleton. An imide skeleton refers to a skeleton containing imide bonds. This imide skeleton can be contained in the main chain of component (A) or in the side chains of component (A). Examples of ways to contain an imide skeleton in the main chain of component (A) include, for example, containing maleimide groups at the ends of the main chain; and examples of ways to contain an imide skeleton inside the main chain. Preferably, component (A) contains an imide skeleton in the main chain, more preferably in the interior of the main chain, or both at the ends and inside the main chain.
[0040] From the viewpoint that a cured product with a lower dielectric loss tangent, which can be achieved by combining (B) inorganic filler material and (C) compound having free radical polymerizable groups, and with a resin composition layer that can further suppress warping after curing and has better reflow solderability, and which can achieve an excellent appearance, component (A) preferably contains the structure shown in the following formula (A-1) as an imide skeleton.
[0041] [Chemistry 3] (In formula (A-1), R) A1 * indicates a tetravalent group obtained by removing the anhydride group from a tetracarboxylic dianhydride; * indicates a linking bond. In equation (A-1), R A1 This indicates a tetravalent group obtained by removing the anhydride group from a tetracarboxylic dianhydride. In R... A1 Of the groups shown, aliphatic tetracarboxylic dianhydrides, aromatic tetracarboxylic dianhydrides, or combinations thereof can be used as tetracarboxylic dianhydrides. Furthermore, one type of tetracarboxylic dianhydride can be used alone, or two or more types can be used in combination. Wherein, R... A1The indicated functional group is preferably a tetravalent group obtained by removing the anhydride group from an aromatic tetracarboxylic dianhydride. Examples of aromatic tetracarboxylic dianhydrides include, for example, phenyltetracarboxylic dianhydride, naphthalenetetracarboxylic dianhydride, anthracenetetracarboxylic dianhydride, and bis(phthalic acid) dianhydride. Examples of bis(phthalic acid) dianhydrides include, for example, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 3,3',4,4'-diphenyl ethertetracarboxylic dianhydride, 3,3',4,4'-diphenyl sulfonetetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,2',3,3'-biphenyltetracarboxylic dianhydride, 2,3,3',4'-biphenyltetracarboxylic dianhydride, 2, 3,3',4'-Benzophenone tetracarboxylic dianhydride, 2,3,3',4'-Diphenyl ether tetracarboxylic dianhydride, 2,3,3',4'-Diphenyl sulfone tetracarboxylic dianhydride, 2,2'-Bis(3,4-dicarboxyphenoxyphenyl)sulfone dianhydride, 4,4'-Oxybisphthalic anhydride, Methylene-4,4'-bisphthalic dianhydride, 1,1-Ethylene-4,4'-bisphthalic dianhydride 2,2-Propylidene-4,4'-Diphthalic anhydride, 1,2-Ethylene-4,4'-Diphthalic anhydride, 1,3-Trimethylene-4,4'-Diphthalic anhydride, 1,4-Tetramethylene-4,4'-Diphthalic anhydride, 1,5-Pentamethylene-4,4'-Diphthalic anhydride, 1,3-Bis(3,4-dicarboxyphenyl)phthalic anhydride, 1,4-bis(3,4-dicarboxyphenyl)phthalic anhydride, 1,3-bis(3,4-dicarboxyphenoxy)phthalic anhydride, 1,4-bis(3,4-dicarboxyphenoxy)phthalic anhydride, 2,2-bis(2,3-dicarboxyphenyl)propane dianhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, 4,4'-(4,4'-isopropylidenediphenoxy)bisphthalic anhydride, etc.
[0042] In a more suitable implementation method, R A1 The group shown is preferably a tetravalent group as shown in formula (A-2-1) or formula (A-2-2).
[0043] [Chemistry 4] (In equations (A-2-1) and (A-2-2), R) A2 Indicates a single bond or a divalent linker; n A2 * indicates 0, 1, or 2; * indicates a hyphen.
[0044] In equation (A-2-1), n A2 Represents 0, 1, or 2. Where n A2 Preferably 0 or 1.
[0045] In equation (A-2-2), R A2 This indicates a single bond or a divalent linker. As R...A2 The divalent linking groups shown can be categorized as those formed from one or more (e.g., 1 to 3000, 1 to 1000, 1 to 100, 1 to 50) skeletal atoms selected from carbon, oxygen, nitrogen, and sulfur atoms. Examples of divalent linking groups include alkylene, alkenylene, arylene, heteroarylene, -O-, -C(=O)-, -C(=O)-O-, and -N(R)-. X )-(Here, R X -C(=O)-NH-, -N(R) X )-C(=O)-N(R) X -, -S-, -S(=O)-, -S(O)2-, etc., can be groups obtained by combining multiple of them. Among them, R A2 The indicated functional groups are preferably single bonds, -O-, -C(=O)- or -C(=O)-O-CH2-CH2-OC(=O)-.
[0046] From the viewpoint of achieving a cured product with a lower dielectric loss tangent, further suppression of warpage after curing, and better reflow soldering resistance by combining (B) inorganic filler material and (C) compounds with free radical polymerizable groups, (A) component preferably contains one or more structural units selected from polyolefin structural units, polycarbonate structural units, polyether structural units, polyester structural units, poly(meth)acrylic acid structural units, and polysiloxane structural units.
[0047] Examples of polyolefin structural units include polyethylene, polypropylene, polybutadiene, hydrogenated polybutadiene, polyisopropylene, and hydrogenated polyisopropylene. Here, "hydrogenated polybutadiene structural unit" refers to a structural unit obtained by hydrogenating some or all of the unsaturated bonds of a polybutadiene structural unit; similarly, "hydrogenated polyisoprene structural unit" refers to a structural unit obtained by hydrogenating some or all of the unsaturated bonds of a polyisoprene structural unit.
[0048] For example, when using a polyol compound containing a polyolefin structure to manufacture component (A), the polyolefin structural unit can be a residual structural unit obtained by removing two or more hydroxyl groups from the polyol compound containing the polyolefin structure. Commercially available polyol compounds containing polyolefin structures can be used, such as those manufactured by Nippon Soda Corporation, including "G-1000", "G-2000", "G-3000" (two-terminated hydroxyl polybutadiene), "GI-1000", "GI-2000", and "GI-3000" (two-terminated hydroxyl hydrogenated polybutadiene).
[0049] Examples of polycarbonate structural units include aliphatic polycarbonates (polyethylene carbonate, polypropylene carbonate, polybutylene carbonate, polycyclohexane carbonate, etc.) and aromatic polycarbonates (polybisphenol A carbonate, polybisphenol F carbonate, polybisphenol S carbonate, etc.).
[0050] For example, when using a polyol compound containing a polycarbonate structure to manufacture component (A), the polycarbonate structural unit can be a residual structural unit obtained by removing two or more hydroxyl groups from the polyol compound containing the polycarbonate structure. Commercially available polyol compounds containing a polycarbonate structure can be used, such as Asahi Kasei Chemicals' "T6002" and "T6001" (two-terminated hydroxyl polycarbonate); and Kuraray's "C-1090," "C-2015N," "C-2090," and "C-3090" (two-terminated hydroxyl polycarbonate).
[0051] Examples of polyether structural units include polyethylene glycol, polypropylene glycol, polytetramethylene glycol, and polybutanediol.
[0052] For example, when using a polyol compound containing a polyether structure to manufacture component (A), the polyether structural unit can be the remaining structural unit obtained by removing two or more hydroxyl groups from the polyol compound containing the polyether structure. Commercially available polyol compounds containing polyether structures can be used, and examples of such commercially available products include, for instance, "PLONON#102", "PLONON#104", "PLONON#201", "PLONON#202B", "PLONON#204", "PLONON#208", "UNILUBE 70DP-600B", and "UNILUBE 70DP-950B" (polyethylene glycol-polypropylene glycol copolymer) manufactured by Nippon Oil Co., Ltd.; and "Pluronic (registered trademark) L-23", "Pluronic (registered trademark) L-31", "Pluronic (registered trademark) L-44", "Pluronic (registered trademark) L-61", and "ADEKA" manufactured by ADEKA Co., Ltd. “Pluronic (registered trademark) L-62”, “Pluronic (registered trademark) L-64”, “Pluronic (registered trademark) L-71”, “Pluronic (registered trademark) L-72”, “Pluronic (registered trademark) L-101”, “Pluronic (registered trademark) L-121”, “Pluronic (registered trademark) P-84”, “Pluronic (registered trademark) P-85”, “Pluronic (registered trademark) P-103”, “Pluronic (registered trademark) F-68”, “Pluronic (registered trademark) F-88”, “Pluronic (registered trademark) F-108”, “Pluronic (registered trademark) 25R-1”, “Pluronic (registered trademark) 25R-2”, “Pluronic (registered trademark) 17R-2”, “Pluronic (registered trademark) 17R-3”, “Pluronic (registered trademark) 17R-4” (polyethylene glycol-polypropylene glycol copolymer).
[0053] Examples of polyester structural units include polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, and polytrimethylene terephthalate.
[0054] For example, when using a polyol compound containing a polyester structure to manufacture component (A), the polyester structure unit can be a residual structure unit obtained by removing two or more hydroxyl groups from the polyol compound containing the polyester structure. Commercially available polyol compounds containing polyester structures can be used, such as Bailon (registered trademark) manufactured by Toyobo Co., Ltd., Polyester (registered trademark) manufactured by Nippon Synthetic Chemical Industry Co., Ltd., and Slack (registered trademark) manufactured by Hitachi Chemical Polymer Co., Ltd.
[0055] A poly(meth)acrylic acid structural unit refers to a structural unit that includes at least one of a plurality of acrylic acid structures and a methacrylic acid structure. For example, when using a polyol compound containing a poly(meth)acrylic acid structure to manufacture component (A), the poly(meth)acrylic acid structural unit can be the remaining structural unit obtained by removing two or more hydroxyl groups from the polyol compound containing the poly(meth)acrylic acid structure. Commercially available products can be used polyol compounds containing poly(meth)acrylic acid structures, such as Nagase ChemteX Corporation's Teisanne "SG-600TEA" and "SG-790" (hydroxyl-containing acrylate copolymer resin), and Negami Kogyo Co., Ltd.'s "W-197C" (hydroxyl-containing acrylate copolymer resin).
[0056] Examples of polysiloxane structural units include dialkyl polysiloxane structural units, diaryl polysiloxane structural units, monoalkyl monoaryl polysiloxane structural units, and monoalkyl polysiloxane structural units.
[0057] For example, when using a polyol compound containing a polysiloxane structure to manufacture component (A), the polysiloxane structural unit can be the remaining structural unit obtained by removing two or more hydroxyl groups from the polyol compound containing the polysiloxane structure. Commercially available products can be used polyol compounds containing a polysiloxane structure; examples of such commercially available products include, for instance, "X-21-5841" and "KF-9701" (two-terminated hydroxyl polysiloxane) manufactured by Shin-Etsu Chemical Industry Co., Ltd.
[0058] From the viewpoint that a cured product with a lower dielectric loss tangent, which can be achieved by combining (B) inorganic filler material and (C) compound having free radical polymerizable groups, and with a resin composition layer that has a superior appearance, can be achieved, the composition (A) preferably contains the structure shown in the following formula (A-3), and preferably combines the structure shown in the above formula (A-1) and the structure shown in the following formula (A-3).
[0059] [Chemistry 5] (In formula (A-3), R) A3 * indicates a divalent group obtained by removing two hydroxyl groups from a polyol compound having two or more hydroxyl groups in one molecule; * indicates a linking bond.
[0060] In equation (A-3), R A3 This refers to the divalent group obtained by removing two hydroxyl groups from a polyol compound having two or more alcoholic hydroxyl groups in one molecule. In R... A3 The indicated groups, as polyol compounds, preferably contain one or more structural units selected from polyolefin, polycarbonate, polyether, polyester, poly(meth)acrylic acid, and polysiloxane structural units; more preferably, contain one or more structural units selected from polyolefin, polycarbonate, polyether, polyester, and polysiloxane structural units; even more preferably, contain one or more structural units selected from polyolefin, polycarbonate, and polysiloxane structural units; and even more preferably, contain a polyolefin structural unit. A single polyol compound may be used alone, or two or more may be used in combination. The polyolefin, polycarbonate, polyether, polyester, poly(meth)acrylic acid, and polysiloxane structural units are as described above.
[0061] In a suitable embodiment, the structure shown in formula (A-3) above can be obtained by polycondensation of a polyol compound having two or more hydroxyl groups in one molecule with a polyisocyanate compound. Examples of such polyisocyanates include, for instance, aliphatic diisocyanate compounds such as butane diisocyanate, hexamethylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, and 2,4,4-trimethylhexamethylene diisocyanate; alicyclic diisocyanate compounds such as norbornene diisocyanate, isophorone diisocyanate, hydrogenated phenylenediamine diisocyanate, and hydrogenated diphenylmethane diisocyanate; phenylenediamine diisocyanates such as p-phenylene diisocyanate or m-phenylene diisocyanate; xylene diisocyanates such as p-xylene diisocyanate or m-xylene diisocyanate; and toluene-2,4-diisocyanate or toluene-2,6-diisocyanate. Toluene diisocyanates such as isocyanates; 4,4'-diphenylmethane diisocyanate, 3,3'-dimethyldiphenyl-4,4'-diisocyanate, 3,3'-diethyldiphenyl-4,4'-diisocyanate, m-xylene diisocyanate, 1,3-bis(α,α-dimethylisocyanate-methyl)benzene, tetramethylphenyldimethyl diisocyanate, diphenyl ether-4,4'-diisocyanate, naphthalene diisocyanate, aromatic diisocyanate compounds; polymethylene polyphenyl polyisocyanates having repeating structures as shown in formula (A-4); their isocyanurate modified forms, biuret modified forms, urea-formaldehyde modified forms, etc. Polyisocyanate compounds can be used alone or in combination of two or more.
[0062] [Chemistry 6] (In formula (A-4), R) A41 Each independently represents an alkyl group having 1 to 4 carbon atoms; R A42 Each can independently represent a hydrogen atom or a monovalent hydrocarbon group with 1 to 6 carbon atoms; n A41 n represents an integer from 0 to 1 to 3. A42 Represents an integer from 1 to 15; * represents a concatenation key. Among them, the polyisocyanate compound capable of realizing the structure shown in formula (A-3) is preferably an alicyclic diisocyanate compound, and more preferably isophorone diisocyanate.
[0063] From the viewpoint that a cured product with a lower dielectric loss tangent, which can be achieved by combining (B) inorganic filler material and (C) compound having free radical polymerizable groups, and with a resin composition layer that has a superior appearance, can be achieved. Component (A) preferably has the structure shown in the following formula (A-5).
[0064] [Chemistry 7] (In formula (A-5), n) A5 Represents an integer from 4 to 90; * represents a hyphen.
[0065] (A) There is no limitation on the method for manufacturing high molecular weight, low elasticity compounds with free radical polymerizable groups at the ends. Furthermore, (A) high molecular weight, low elasticity compounds with free radical polymerizable groups at the ends can be purchased commercially.
[0066] The content of component (A) in the resin composition is preferably 0.1% by mass or more, more preferably 1% by mass or more, further preferably 2% by mass or more, and preferably 30% by mass or less, more preferably 20% by mass or less, and further preferably 15% by mass or less, relative to 100% by mass of the total of components (A) to (C). When the content of component (A) is within the above range, the dielectric loss tangent in the cured resin composition can be reduced, exhibiting excellent reflow soldering resistance, and warping after curing can be particularly suppressed.
[0067] When the resin composition contains components other than (A) to (C), the content of component (A) in the resin composition is preferably 0.1% by mass or more, more preferably 1% by mass or more, further preferably 2% by mass or more, and preferably 30% by mass or less, more preferably 20% by mass or less, and further preferably 15% by mass or less, relative to 100% by mass of the non-volatile components of the resin composition. When the content of component (A) is within the above range, the dielectric loss tangent of the cured resin composition can be reduced, exhibiting excellent reflow soldering resistance, and warping after curing can be particularly suppressed.
[0068] When the resin composition contains components other than (A) to (C), the content of component (A) in the resin composition is preferably 1% by mass or more, more preferably 3% by mass or more, further preferably 5% by mass or more or 7% by mass or more, and preferably 60% by mass or less, more preferably 50% by mass or less, and further preferably 45% by mass or less, relative to 100% by mass of the resin composition. When the content of component (A) is within the above range, the dielectric loss tangent of the cured resin composition can be reduced, exhibiting excellent reflow soldering resistance, and warping after curing can be particularly suppressed.
[0069] <(B) Inorganic filler materials> In the resin composition of the present invention, component (B) comprises an inorganic filler. The inorganic filler (B) does not include any of the components belonging to component (A) above. The inorganic filler (B) is contained in the resin composition in particulate form and is contained in the cured product while maintaining its particulate morphology. In the resin composition of the present invention, component (B) may be used alone or in combination of two or more.
[0070] Inorganic compounds can be used as materials for (B) inorganic filler. Examples of materials for (B) inorganic filler include, for example, silicon dioxide, alumina, glass, cordierite, silicon oxide, barium sulfate, barium carbonate, talc, clay, mica powder, zinc oxide, hydrotalcite, boehmite, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum nitride, manganese nitride, aluminum borate, strontium carbonate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, zirconium oxide, barium titanate, barium zirconate titanate, barium zirconate, calcium zirconate, zirconium phosphate, and zirconium tungstate phosphate. Among these, materials selected from one or more of silicon dioxide and alumina are suitable, with silicon dioxide being particularly suitable. Examples of silicon dioxide include, for example, amorphous silicon dioxide, fused silicon dioxide, crystalline silicon dioxide, synthetic silicon dioxide, and hollow silicon dioxide. Furthermore, spherical silicon dioxide is preferred as silicon dioxide.
[0071] Commercially available products as (B) inorganic filler materials include, for example, “SP60-05” and “SP507-05” manufactured by Nippon Steel Kemica & Materia; “YC100C”, “YA050C”, “YA050C-MJE”, “YA010C”, “SC2500SQ”, “SO-C4”, “SO-C2”, and “SO-C1” manufactured by Admatechs; “UFP-30”, “DAW-03”, and “FB-105FD” manufactured by Denka; “SILFIL NSS-3N”, “SILFIL NSS-4N”, and “SILFIL NSS-5N” manufactured by Tokuyama; “Cellspheres” and “MGH-005” manufactured by Pacific Cement; and “HIPRESICAFH” manufactured by Ube Exsymo.
[0072] (B) The average particle size of the inorganic filler material is not particularly limited, but is preferably 10 μm or less, more preferably 5 μm or less, and even more preferably 3 μm or less, 2 μm or less, 1 μm or less, or 0.7 μm or less. The lower limit of this average particle size is not particularly limited, but is preferably 0.01 μm or more, more preferably 0.05 μm or more, and even more preferably 0.07 μm or more, 0.1 μm or more, or 0.2 μm or more. (B) The average particle size of the inorganic filler material can be determined by laser diffraction / scattering based on the Mie scattering theory. Specifically, the particle size distribution of the inorganic filler material can be prepared according to a volume basis using a laser diffraction scattering particle size distribution measuring device, and the median particle size can be used as the average particle size for measurement. The sample for measurement can be obtained by weighing 100 mg of the inorganic filler material and 10 g of methyl ethyl ketone into a vial and dispersing it using ultrasound for 10 minutes. For the sample being measured, a laser diffraction particle size distribution measuring device is used. The light source wavelength is set to blue and red, and the particle size distribution of the inorganic filler material is measured using a flow cell method based on a volume reference. The average particle size is calculated from the obtained particle size distribution in the form of median particle size. Examples of laser diffraction particle size distribution measuring devices include the "LA-960" manufactured by Horiba Manufacturing Co., Ltd.
[0073] (B) The specific surface area of the inorganic filler material is not particularly limited, but is preferably 0.1 m². 2 / g or more, preferably 0.5m 2 / g or more, further preferably 1m 2 / g or more, 3m 2 / g or more or 5m 2 / g or more. There is no particular upper limit to this specific surface area, but it is preferably 100m². 2 / g or less, preferably 80m 2 / g or less, more preferably 60m 2 / g or less, 50m 2 / g or less or 40m 2 / g or less. (D) The specific surface area of the component was obtained by adsorbing nitrogen onto the sample surface using a specific surface area measuring device (Macsorb HM-1210 manufactured by Mountech) according to the BET method, and calculating the specific surface area using the BET multi-point method.
[0074] (B) The inorganic filler material is preferably surface-treated with a suitable surface treatment agent. Surface treatment improves the moisture resistance and dispersibility of the (B) inorganic filler material. Examples of surface treatment agents include, for instance, vinyl silane coupling agents, epoxy silane coupling agents, styrene silane coupling agents, (meth)acrylic silane coupling agents, amino silane coupling agents, isocyanurate silane coupling agents, urea silane coupling agents, mercapto silane coupling agents, isocyanate silane coupling agents, anhydride silane coupling agents, and other silane coupling agents; non-silane coupling-alkoxysilane compounds such as methyltrimethoxysilane and phenyltrimethoxysilane; and silazane compounds. One surface treatment agent may be used alone, or two or more may be used in combination.
[0075] Commercially available surface treatment agents include, for example, "KBM403" (3-epoxypropoxypropyltrimethoxysilane) manufactured by Shin-Etsu Chemical Industry Co., Ltd., "KBM803" (3-mercaptopropyltrimethoxysilane) manufactured by Shin-Etsu Chemical Industry Co., Ltd., "KBE903" (3-aminopropyltriethoxysilane) manufactured by Shin-Etsu Chemical Industry Co., Ltd., "KBM573" (N-phenyl-3-aminopropyltrimethoxysilane) manufactured by Shin-Etsu Chemical Industry Co., Ltd., and "SZ-31" (hexamethyldisilazane) manufactured by Shin-Etsu Chemical Industry Co., Ltd.
[0076] From the viewpoint of improving the dispersibility of inorganic filler materials, the degree of surface treatment using a surface treatment agent is preferably within a specified range. Specifically, it is preferred that 100% by mass of the inorganic filler material is surface treated with 0.2% to 5% by mass of a surface treatment agent.
[0077] The degree of surface treatment using surface treatment agents can be evaluated based on the carbon content per unit surface area of the inorganic filler. From the viewpoint of improving the dispersibility of the inorganic filler, the carbon content per unit surface area of the inorganic filler is preferably 0.02 mg / m². 2 The above, more preferably 0.1 mg / m 2 The above is further preferred to be 0.2 mg / m³. 2 That's all. On the other hand, from the viewpoint of preventing an increase in the melt viscosity of the resin composition and the melt viscosity in flake form, (B) the upper limit of the carbon content per unit surface area of the inorganic filler is preferably 1 mg / m². 2 The following is more preferably 0.8 mg / m³ 2 The following is a further preferred value: 0.5 mg / m³ 2The following is an explanation of the carbon content per unit surface area of inorganic filler materials. (B) The carbon content per unit surface area of the inorganic filler material can be determined by cleaning the surface-treated inorganic filler material with a solvent (e.g., methyl ethyl ketone (MEK)). Specifically, a sufficient amount of MEK is added to the surface-treated inorganic filler material, and the material is ultrasonically cleaned at 25°C for 5 minutes. After removing the supernatant and drying the solid components, the carbon content per unit surface area of the inorganic filler material can be determined using a carbon analyzer. A carbon analyzer such as the "EMIA-320V" manufactured by Horiba Manufacturing Co., Ltd. can be used.
[0078] The content of component (B) in the resin composition is preferably 50% by mass or more, more preferably 55% by mass or more, even more preferably 60% by mass or more, preferably 90% by mass or less, more preferably 85% by mass or less, even more preferably 83% by mass or less or 82% by mass or less, relative to the total mass of components (A) to (C) in 100% by mass. When the content of component (B) is within the above range, the dielectric loss tangent of the cured resin composition can be reduced, exhibiting excellent reflow soldering resistance, and warping after curing can be particularly suppressed.
[0079] When the resin composition contains components other than (A) to (C), the content of component (B) in the resin composition is preferably 50% by mass or more, more preferably 55% by mass or more, further preferably 60% by mass or more, and preferably 90% by mass or less, more preferably 85% by mass or less, further preferably 83% by mass or less, or 82% by mass or less, relative to 100% by mass of the non-volatile components of the resin composition. When the content of component (B) is within the above range, the dielectric loss tangent of the cured resin composition can be reduced, exhibiting excellent reflow soldering resistance, and warping after curing can be particularly suppressed.
[0080] <(C) Compounds with free radical polymerizable groups (compounds with free radical polymerizable groups and a weight-average molecular weight (Mw) of less than 5,000)> In the resin composition of the present invention, component (C) comprises a compound having a free radical polymerizable group. Unless otherwise stated, the compound having a free radical polymerizable group in component (C) does not include components belonging to components (A) and (B) above. That is, the weight-average molecular weight (Mw) of component (C) is 5,000 or less. In the resin composition of the present invention, component (C) may be used alone or in combination of two or more.
[0081] (C) The weight-average molecular weight (Mw) of the compound having free radical polymerizable groups is 5,000 or less, preferably 4,000 or less, and more preferably 3,000 or less. The lower limit is not particularly limited; for example, it can be 150 or more. (C) The weight-average molecular weight of the compound having free radical polymerizable groups can be determined by gel permeation chromatography (GPC) in the form of a polystyrene equivalent.
[0082] As component (C), there is no particular limitation on the type of free radical polymerizable group, as long as it has one or more (preferably two or more) free radical polymerizable groups in one molecule. Examples of components (C) include compounds having one or more free radical polymerizable groups selected from vinyl, allyl, vinylphenyl, (meth)acryloyl, and maleimide. When component (C) contains two or more free radical polymerizable groups, these two or more free radical polymerizable groups may be the same or different.
[0083] (C) The compound having a free radical polymerizable group preferably includes one or more compounds selected from maleimide-based free radical polymerizable compounds, (meth)acrylic acid-based free radical polymerizable compounds, styrene-based free radical polymerizable compounds and allyl-based free radical polymerizable compounds, more preferably including maleimide-based free radical polymerizable compounds.
[0084] Maleimide-based free radical polymerizable compounds are, for example, compounds having one or more, preferably two or more, maleimide groups. Maleimide-based free radical polymerizable compounds can be aliphatic maleimide compounds containing an aliphatic amine skeleton, or aromatic maleimide compounds containing an aromatic amine skeleton. Commercially available maleimide-based free radical polymerizable compounds include, for example, Shin-Etsu Chemical Co., Ltd.'s "SLK-2600" and "SLK-6895-T90"; Designer Molecules Inc.'s "BMI-1500", "BMI-1700", "BMI-3000J", "BMI-689", and "BMI-2500" (maleimide compounds containing dimerized diamine structures); Designer Molecules Inc.'s "BMI-6100" (aromatic maleimide compound); Nippon Kayaku Co., Ltd.'s "MIR-5000-60T" and "MIR-3000-70MT" (biphenyl aralkyl maleimide compounds); Kei Ai Chemical Co., Ltd.'s "BMI-70" and "BMI-80"; and Daiwa Chemical Industry Co., Ltd.'s "BMI-2300" and "BMI-TMH", etc. Alternatively, as a maleimide-based free radical polymerizable compound, the maleimide resin (a maleimide compound containing an indane ring skeleton) disclosed in Patent Application Publication No. 2020-500211 can be used.
[0085] (Meth)acrylic acid-based free radical polymerizable compounds are, for example, compounds having one or more, preferably two or more, acryloyl and / or methacryloyl groups. Examples of (meth)acrylic acid-based free radical polymerizable compounds include, for instance, cyclohexane-1,4-diethanol di(meth)acrylate, cyclohexane-1,3-diethanol di(meth)acrylate, tricyclodecanediethanol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,8-octanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, glycerol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, and other aliphatic (meth)acrylate compounds; dioxanediol di(meth)acrylate... Ether-containing (meth)acrylate compounds such as esters, 3,6-dioxa-1,8-octanediol di(meth)acrylate, 3,6,9-trioxaundecane-1,11-diol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, 9,9-bis[4-(2-acryloyloxyethoxy)phenyl]fluorene, ethoxylated bisphenol A di(meth)acrylate, propoxylated bisphenol A di(meth)acrylate, etc.; (meth)acrylate compounds containing isocyanurate groups such as tri(3-hydroxypropyl)isocyanurate tri(meth)acrylate, tri(2-hydroxyethyl)isocyanurate tri(meth)acrylate, ethoxylated isocyanuric acid tri(meth)acrylate, etc.; acrylate compounds such as (meth)acrylate-modified polyphenylene ether resins, etc. Commercially available (meth)acrylic acid-based free radical polymerizable compounds include, for example, "A-DOG" (dioxanediol diacrylate) manufactured by Shin-Nakamura Chemical Industry Co., Ltd., "DCP-A" (tricyclodecanediethanol diacrylate) and "DCP" (tricyclodecanediethanol dimethacrylate) manufactured by Kyoeisha Chemical Co., Ltd., "KAYARAD R-684" (tricyclodecanediethanol diacrylate) and "KAYARAD R-604" (dioxanediol diacrylate) manufactured by Nippon Kayaku Co., Ltd., and "SA9000" and "SA9000-111" (methacrylic acid-modified polyphenylene ether) manufactured by SABIC.
[0086] Examples of styrene-based free radical polymerizable compounds include compounds having one or more, preferably two or more, vinyl groups directly bonded to an aromatic carbon atom. Examples of styrene-based free radical polymerizable compounds include divinylbenzene, 2,4-divinyltoluene, 2,6-divinylnaphthalene, 1,4-divinylnaphthalene, 4,4'-divinylbiphenyl, 1,2-bis(4-vinylphenyl)ethane, 2,2-bis(4-vinylphenyl)propane, bis(4-vinylphenyl) ether, vinylbenzyl-modified polyphenylene ether resin, and styrene-divinylbenzene copolymers. Commercially available styrene-based free radical polymerizable compounds include, for example, "ODV-XET (X03)," "ODV-XET (X04)," and "ODV-XET (X05)" (styrene-divinylbenzene copolymer) manufactured by Nippon Steel Kemica & Materia; and "OPE-2St," "OPE-2St 1200," and "OPE-2St 2200" (vinylbenzyl modified polyphenylene ether resin) manufactured by Mitsubishi Gas Chemical Co., Ltd.
[0087] Allyl-based free radical polymerizable compounds are, for example, compounds having one or more allyl groups, preferably two or more. Examples of allyl-based free radical polymerizable compounds include, for instance, allyl biphenylate, triallyl trimellitate, diallyl phthalate, diallyl isophthalate, diallyl terephthalate, diallyl 2,6-naphthalenedicarboxylate, diallyl 2,3-naphthalenedicarboxylate, and other aromatic carboxylic acid allyl ester compounds; 1,3,5-triallyl isocyanurate, 1,3-diallyl-5-glycidyl isocyanurate, and other isocyanurate allyl ester compounds; 2,2- Aromatic allyl compounds containing epoxy groups, such as bis[3-allyl-4-(glycidyloxy)phenyl]propane; aromatic allyl compounds containing benzoxazine, such as bis[3-allyl-4-(3,4-dihydro-2H-1,3-benzoxazine-3-yl)phenyl]methane; aromatic allyl compounds containing ethers, such as 1,3,5-triallyl ether benzene; allyl silane compounds, such as diallyl diphenylsilane; and resins containing multiple benzene rings and allyl groups, respectively. Commercially available allyl-based free radical polymerizable compounds include, for example, TAIC (1,3,5-triallyl isocyanurate) manufactured by Nippon Chemical Co., Ltd.; DAD (diallyl biphenyl) manufactured by Nippon Techno Fine Chemical Co., Ltd.; TRIAM-705 (triallyl trimellitate) manufactured by Fujifilm and Koujun Pharmaceutical Co., Ltd.; DAND (diallyl 2,3-naphthylcarboxylate) manufactured by Nippon Techno Fine Chemical Co., Ltd.; RE-810NM (2,2-bis[3-allyl-4-(glycidyloxy)phenyl]propane) manufactured by Nippon Chemical Co., Ltd.; DA-MGIC (1,3-diallyl-5-glycidyl isocyanurate) manufactured by Shikoku Chemical Industry Co., Ltd.; and NE-V-1100-70T (a resin containing multiple benzene rings and allyl groups) manufactured by DIC Co., Ltd.
[0088] (C) The free radical polymerizable group equivalent of the compound having a free radical polymerizable group is preferably 20 g / eq. to 3,000 g / eq., more preferably 50 g / eq. to 2,500 g / eq., even more preferably 70 g / eq. to 2,000 g / eq., and even more preferably 90 g / eq. to 1,500 g / eq. The free radical polymerizable group equivalent represents the mass of (C) the compound having a free radical polymerizable group per 1 equivalent of free radical polymerizable group.
[0089] The content of component (C) in the resin composition is preferably 5% by mass or more, more preferably 10% by mass or more, even more preferably 12% by mass or more, and preferably 40% by mass or less, more preferably 35% by mass or less, even more preferably 30% by mass or less or 27% by mass or less, relative to the total mass of components (A) to (C) of 100% by mass. When the content of component (C) is within the above range, the dielectric loss tangent of the cured resin composition can be reduced, exhibiting excellent reflow soldering resistance, and warping after curing can be particularly suppressed.
[0090] When the resin composition contains components other than (A) to (C), the content of component (C) in the resin composition is preferably 5% by mass or more, more preferably 10% by mass or more, further preferably 12% by mass or more, and preferably 40% by mass or less, more preferably 35% by mass or less, further preferably 30% by mass or less, or 27% by mass or less, relative to 100% by mass of the non-volatile components of the resin composition. When the content of component (C) is within the above range, the dielectric loss tangent of the cured resin composition can be reduced, exhibiting excellent reflow soldering resistance, and warping after curing can be particularly suppressed.
[0091] When the resin composition contains components other than (A) to (C), the content of component (C) in the resin composition is preferably 40% by mass or more, more preferably 50% by mass or more, further preferably 55% by mass or more, and preferably 95% by mass or less, more preferably 93% by mass or less, and further preferably 91% by mass or less, relative to 100% by mass of the resin composition. When the content of component (C) is within the above range, the dielectric loss tangent of the cured resin composition can be reduced, exhibiting excellent reflow soldering resistance, and warping after curing can be particularly suppressed.
[0092] The ratio of the content of component (A) to the content of component (C) in the resin composition, i.e., the mass ratio of component (A) to component (C) (content of component (A)) / (content of component (C)), is preferably 0.01 or more, more preferably 0.05 or more, even more preferably 0.09 or more, and preferably 1.5 or less, more preferably 1 or less, and even more preferably 0.85 or less. When this mass ratio is within the above range, the dielectric loss tangent in the cured resin composition can be reduced, exhibiting excellent reflow soldering resistance, and warping after curing can be particularly suppressed.
[0093] <(D) Polymerization Initiator> The resin composition of the present invention may include a polymerization initiator (D) as an optional component. Unless otherwise stated, the polymerization initiator (D) does not include components belonging to components (A) through (C) described above. According to the polymerization initiator (D), the reaction between the high molecular weight, low elasticity compound (A) having a terminal free radical polymerizable group and the compound (C) having a free radical polymerizable group can be promoted, thereby promoting the curing of the resin composition. When the resin composition includes a polymerization initiator (D), component (D) may be used alone or in combination of two or more.
[0094] As a (D) polymerization initiator, a compound that can generate free radicals upon heating is used, for example. Examples of (D) polymerization initiators include peroxide-based free radical polymerization initiators and azo-based free radical polymerization initiators, among which peroxide-based free radical polymerization initiators are preferred.
[0095] Examples of peroxide-based free radical polymerization initiators include hydrogen peroxide compounds such as 1,1,3,3-tetramethylbutyl hydroperoxide; dialkyl peroxide compounds such as tert-butylcumyl peroxide, di-tert-butyl peroxide, di-tert-hexyl peroxide, dicumyl peroxide, 1,4-bis(1-tert-butylperoxy-1-methylethyl)benzene, and 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane; and dilauroyl peroxide, didecanoyl peroxide, dicyclohexyl peroxydicarbonate, and bis(4-tert-butylcyclohexyl)peroxide. Diacyl peroxides such as dicarbonates; peroxide esters such as tert-butyl peroxyacetate, tert-butyl peroxybenzoate, tert-butyl peroxyisopropyl monocarbonate, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxyneodecanate, tert-hexyl peroxyisopropyl monocarbonate, tert-butyl peroxylaurate, (1,1-dimethylpropyl)2-ethylperhexanoate, tert-butyl2-ethylperhexanoate, tert-butyl3,5,5-trimethylperhexanoate, tert-butyl peroxy-2-ethylhexyl monocarbonate, and tert-butyl peroxymaleate.
[0096] Examples of azo-based free radical polymerization initiators include 2,2'-azobis(4-methoxy-2,4-dimethylpentanonitrile), 2,2'-azobis(2,4-dimethylpentanonitrile), 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), 1,1'-azobis(cyclohexane-1-carboxynitrile), 1-[(1-cyano-1-methylethyl)azo]formamide, and 2-phenylazo-4-methoxy-2,4-dimethylpentanonitrile; 2,2'-azobis[2-methyl-N-[1,1-bis(hydroxymethyl)-2-hydroxyethyl]propionamide], 2,2'-azobis[2-methyl-N-[1,1-bis(hydroxymethyl)-2-hydroxyethyl]propionamide], and 2,2'-azobis[2-methyl-N-[1,1-bis(hydroxymethyl)-2-hydroxyethyl]propionamide], etc. Azoamide compounds such as [(hydroxymethyl)ethyl]propionamide], 2,2'-azobis[2-methyl-N-[2-(1-hydroxybutyl)]-propionamide], 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)-propionamide], 2,2'-azobis(2-methylpropionamide) dihydrate, 2,2'-azobis[N-(2-propenyl)-2-methylpropionamide], 2,2'-azobis(N-butyl-2-methylpropionamide), 2,2'-azobis(N-cyclohexyl-2-methylpropionamide); alkyl azo compounds such as 2,2'-azobis(2,4,4-trimethylpentane) and 2,2'-azobis(2-methylpropane).
[0097] Commercially available products that serve as (D) polymerization initiators include, for example, "Perbutyl C", "Perbutyl A", "Perbutyl P", "Perbutyl L", "Perbutyl O", "Perbutyl ND", "Perbutyl Z", "Perbutyl I", "Percumyl P", "Percumyl D", "Perhexyl D", "Perhexyl A", "Perhexyl I", "Perhexyl Z", "Perhexyl ND", "Perhexyl O", and "Perhexyl PV" manufactured by Nippon Oil Company; and "Luperox DTA" manufactured by Arkema.
[0098] When the resin composition contains a (D) polymerization initiator, the content of the (D) component in the resin composition is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, even more preferably 0.1% by mass or more, and preferably 3% by mass or less, more preferably 1% by mass or less, and even more preferably 0.5% by mass or less, relative to 100% by mass of the non-volatile components of the resin composition.
[0099] When the resin composition contains a (D) polymerization initiator, the content of the (D) component in the resin composition is preferably 0.1% by mass or more, more preferably 0.3% by mass or more, even more preferably 0.4% by mass or more, and preferably 5% by mass or less, more preferably 3% by mass or less, and even more preferably 1% by mass or less, relative to 100% by mass of the resin component in the resin composition.
[0100] <(E) Polymer Resins> The resin composition of the present invention may include (E) polymeric resin as an optional component. Unless otherwise stated, the (E) polymeric resin, as component (E), does not include components belonging to components (A) through (D) described above. The (E) polymeric resin may be compatible with resin components other than (E) polymeric resin and may be included in the resin composition. When the resin composition includes component (E), component (E) may be used alone or in combination of two or more.
[0101] (E) The weight-average molecular weight (Mw) of the polymer resin is, for example, greater than 5,000, preferably 8,000 or more, more preferably 10,000 or more, further preferably 20,000 or more, and preferably 100,000 or less, more preferably 70,000 or less, and further preferably 60,000 or less. (E) The weight-average molecular weight of the polymer resin can be determined by gel permeation chromatography (GPC) in the form of polystyrene equivalents.
[0102] Examples of (E) polymeric resins include, for example, resins containing oxazoline groups, phenoxy resins, polybutadiene resins, polyimide resins, polyvinyl alcohol acetal resins, polyolefin resins, polyamide-imide resins, polyether-imide resins, polysulfone resins, polyethersulfone resins, polyphenylene ether resins, polycarbonate resins, polyether ether ketone resins, polyester resins, etc. As mentioned above, (E) polymeric resins do not include components belonging to (A) to (D). Therefore, among compounds with a weight-average molecular weight (Mw) exceeding 5,000 and below 300,000, and a tensile modulus of elasticity of 1 GPa or below as measured at 25°C according to JIS K7161, compounds with free radical polymerizable groups at their ends are not (E) components, but are classified as (A) components.
[0103] Resins containing oxazoline groups are obtained by polymerizing, for example, addition polymerizable oxazoline compounds (monomers containing a vinyloxazoline skeleton), such as 2-isopropenyl-2-oxazoline, 5-methyl-2-isopropenyl-2-oxazoline, 4,4-dimethyl-2-isopropenyl-2-oxazoline, 4-methyl-2-isopropenyl-2-oxazoline, 4,4,5-trimethyl-2-isopropenyl-2-oxazoline, 2-vinyl-2-oxazoline, 5-methyl-2-vinyl-2-oxazoline, 4,4-dimethyl-2-vinyl-2-oxazoline, 4-methyl-2-vinyl-2-oxazoline, and 4,4,5-trimethyl-2-vinyl-2-oxazoline. In addition, resins containing oxazoline groups can be copolymerized with styrene monomers such as α-methylstyrene, 4-methylstyrene, 3-methylstyrene, 2-methylstyrene, 4-ethylstyrene, 4-tert-butylstyrene, p-divinylbenzene, and m-divinylbenzene, as needed. Specific examples of resins containing oxazoline groups include "PX-3-RP-61" manufactured by Nippon Shokubai Co., Ltd.
[0104] Examples of phenoxy resins include those having one or more skeletons selected from the following: bisphenol A skeleton, bisphenol F skeleton, bisphenol S skeleton, bisphenol acetophenone skeleton, phenolic varnish skeleton, biphenyl skeleton, fluorene skeleton, dicyclopentadiene skeleton, norbornene skeleton, naphthalene skeleton, anthracene skeleton, adamantane skeleton, terpene skeleton, and trimethylcyclohexane skeleton. The terminal group of a phenoxy resin can be any functional group such as a phenolic hydroxyl group or an epoxy group. Specific examples of phenoxy resins include Mitsubishi Chemical's "1256" and "4250" (both phenoxy resins containing a bisphenol A backbone); Mitsubishi Chemical's "YX8100" (phenoxy resin containing a bisphenol S backbone); Mitsubishi Chemical's "YX6954" (phenoxy resin containing a bisphenol acetophenone backbone); Nippon Steel Kemica & Materia's "FX280" and "FX293"; and Mitsubishi Chemical's "YX7200B35", "YL7500BH30", "YX6954BH30", "YX7553BH30", "YL7769BH30", "YL6794", "YL7213", "YL7290", and "YL7482", etc.
[0105] Examples of polybutadiene resins include resins containing a hydrogenated polybutadiene backbone, polybutadiene resins containing hydroxyl groups, polybutadiene resins containing phenolic hydroxyl groups, polybutadiene resins containing carboxyl groups, polybutadiene resins containing anhydride groups, polybutadiene resins containing epoxy groups, polybutadiene resins containing isocyanate groups, polybutadiene resins containing urethane groups, and polyphenylene ether-polybutadiene resins. It should be noted that polybutadiene resins as component (E) do not include components belonging to component (A). Additionally, polybutadiene resins with phenolic resin end capping can be used.
[0106] As the polyimide resin, resins having an imide structure (preferably a cyclic imide structure) can be used, such as imides of acid anhydrides and diamine compounds, and imides of acid anhydrides and diisocyanate compounds. It should be noted that the polyimide resin as component (E) does not include components belonging to component (A). Among these, the polyimide resin as component (E) is preferably an imide of an acid anhydride and diamine compound. Furthermore, the polyimide resin may contain an indane backbone, such as a trimethyl indane backbone; for example, structural units formed by polymerization of diamine compounds may contain an indane backbone.
[0107] As an acid anhydride used in the manufacture of polyimide resins, tetracarboxylic acid anhydrides are preferred. Examples of tetracarboxylic acid anhydrides include aromatic tetracarboxylic acid dianhydrides and aliphatic tetracarboxylic acid dianhydrides, with aromatic tetracarboxylic acid dianhydrides being preferred. Examples of aromatic tetracarboxylic acid dianhydrides include phenyltetracarboxylic acid dianhydrides, naphthalenetetracarboxylic acid dianhydrides, anthracenetetracarboxylic acid dianhydrides, and bis(phthalic acid) dianhydrides, with bis(phthalic acid) dianhydrides being preferred. Examples of bis(phthalic acid) dianhydrides include 3,3',4,4'-benzophenone tetracarboxylic acid dianhydrides, 3,3',4,4'-diphenyl ether tetracarboxylic acid dianhydrides, 3,3',4,4'-diphenyl sulfone tetracarboxylic acid dianhydrides, 3,3',4,4'-biphenyltetracarboxylic acid dianhydrides, 2,2',3,3'-biphenyltetracarboxylic acid dianhydrides, 2,3',4'-biphenyltetracarboxylic acid dianhydrides, and 2,3',4'-biphenyltetracarboxylic acid dianhydrides. 3',4'-Benzophenone tetracarboxylic dianhydride, 2,3,3',4'-Diphenyl ether tetracarboxylic dianhydride, 2,3,3',4'-Diphenyl sulfone tetracarboxylic dianhydride, 2,2'-Bis(3,4-dicarboxyphenoxyphenyl)sulfone dianhydride, 4,4'-Oxybisphthalic anhydride, Methylene-4,4'-bisphthalic dianhydride, 1,1-Ethylene-4,4'-bisphthalic dianhydride 2,2-Propylidene-4,4'-Diphthalic anhydride, 1,2-Ethylene-4,4'-Diphthalic anhydride, 1,3-Trimethylene-4,4'-Diphthalic anhydride, 1,4-Tetramethylene-4,4'-Diphthalic anhydride, 1,5-Pentamethylene-4,4'-Diphthalic anhydride, 1,3-Bis(3,4-dicarboxyphenyl)phthalic anhydride, 1,4-bis(3,4-dicarboxyphenyl)phthalic anhydride, 1,3-bis(3,4-dicarboxyphenoxy)phthalic anhydride, 1,4-bis(3,4-dicarboxyphenoxy)phthalic anhydride, 2,2-bis(2,3-dicarboxyphenyl)propane dianhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, 4,4'-(4,4'-isopropylidenediphenoxy)bisphthalic anhydride, etc.
[0108] Examples of diamine compounds used in the manufacture of polyimide resins include aliphatic and aromatic diamine compounds, with aromatic diamine compounds being preferred. Examples of diphenylamine compounds include 4,4'-diamino-2,2'-bis(trifluoromethyl)-1,1'-biphenyl, 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl ether, 3,3'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfide, 4-aminophenyl-4-aminobenzoate, 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 2,2-bis(4-aminophenyl)propane, 4,4'-(hexafluoroisopropylidene)diphenylamine, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 2,2-bis[4-(4-aminophenoxy)propane, etc. [4,4'-(4-aminophenoxy)phenyl]hexafluoropropane, α,α-bis[4-(4-aminophenoxy)phenyl]-1,3-diisopropylbenzene, α,α-bis[4-(4-aminophenoxy)phenyl]-1,4-diisopropylbenzene, 4,4'-(9-fluoreneyl)diphenylamine, 2,2-bis(3-methyl-4-aminophenyl)propane, 2,2-bis(3-methyl-4-aminophenyl)benzene, 4,4'-diamino-3,3'-dimethyl-1,1'-biphenyl, 4,4'-diamino-2,2'-dimethyl-1,1'-biphenyl, 9,9'-bis(3-methyl-4-aminophenyl)fluorene, 5-(4-aminophenoxy)-3-[4-(4-aminophenoxy)phenyl]-1,1,3-trimethylindene, etc.
[0109] Examples of commercially available polyimide resins include "Rikakot SN20" and "Rikakot PN20" manufactured by Shin Nippon Rika Co., Ltd. Other examples of polyimide resins include linear polyimides (substances described in Japanese Patent Application Publication No. 2006-37083) obtained by reacting difunctional hydroxyl-terminated polybutadiene, diisocyanate compounds, and tetrabasic anhydrides, and modified polyimides containing a polysiloxane backbone (substances described in Japanese Patent Application Publication Nos. 2002-12667 and 2000-319386, etc.).
[0110] (E) The polymer resin may contain an elastomer. The elastomer is a resin with flexibility, preferably a resin with rubber elasticity or a resin that exhibits rubber elasticity by polymerization with other components. Examples of rubber elasticity include resins that exhibit an elastic modulus of 1 GPa or less when subjected to a tensile test according to Japanese Industrial Standard (JIS K7161) at a temperature of 25°C and a humidity of 40% RH. More specifically, the aforementioned elastic modulus of the elastomer is, for example, 1 GPa or less, preferably 0.9 GPa or less, more preferably 0.8 GPa or less, further preferably 0.7 GPa or less, and preferably 0.01 GPa or more, more preferably 0.03 GPa or more, further preferably 0.05 GPa or more, and even more preferably 0.1 GPa or more.
[0111] The elastomer is preferably selected from one or more resins with a glass transition temperature (Tg) of 25°C or less and resins that are liquid at 25°C or less. The glass transition temperature of the resin with a Tg of 25°C or less is preferably 20°C or less, more preferably 15°C or less. The lower limit of the glass transition temperature is not particularly limited, and for example, it can be -15°C or more. Furthermore, as a resin that is liquid at 25°C, a resin that is liquid at 20°C or less is preferred, more preferably a resin that is liquid at 15°C or less. The glass transition temperature can be determined by DSC (differential scanning calorimetry).
[0112] (E) The polymeric resin is compatible with resin components other than the (E) polymeric resin and can be contained in the resin composition. Such compatible (E) polymeric resin can be contained in the cured body in a granular form. Alternatively, the (E) polymeric resin can be contained in the resin composition in a particulate state, and is incompatible with resin components other than the (E) polymeric resin. Such particulate (E) polymeric resin can be contained in the cured body in a particulate state, and is incompatible with resin components other than the (E) polymeric resin. Furthermore, a (E) polymeric resin compatible with resin components other than the (E) polymeric resin and a particulate (E) polymeric resin can be used in combination.
[0113] Examples of particulate (E) polymer resins include rubber particles, polyamide microparticles, silicone particles, and core-shell particles. Rubber particles and core-shell particles are preferred, with core-shell particles being more preferred. Core-shell particles are particulate polymer resins having a core particle and one or more shell layers covering it. Core-shell particles are preferably core-shell graft copolymer particles having a resin-containing core particle and a shell layer grafted with monomer components capable of copolymerizing with the resin contained in the core particle. Here, "core-shell type" does not necessarily refer only to types where the core particle and shell layer are clearly distinguishable, but also includes types where the boundary between the core particle and shell layer is unclear. Furthermore, the core particle may not be completely covered by the shell layer.
[0114] Commercially available products of core-shell graft copolymer particles include, for example, Samsung SDI's "CHT"; Techno UMG's "B602"; Dow Chemical Japan's "PARALOID EXL2602", "PARALOID EXL2603", "PARALOID EXL2655", "PARALOID EXL2311", "PARALOID EXL2313", "PARALOID EXL2315", "PARALOID KM330", "PARALOID KM336P", and "PARALOID KCZ201"; Mitsubishi Rayon's "METABLEN C-223A", "METABLEN E-901", "METABLEN S-2001", "METABLEN W-450A", and "METABLEN SRK-200"; and KANEKA's "KANE ACE M-511", "KANE ACE M-600", and "KANE ACE M-600". M-400", "KANE ACE M-580", "KANE ACE MR-01", etc.
[0115] When the resin composition contains (E) polymeric resin, the content of (E) component in the resin composition is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, even more preferably 0.9% by mass or more, and preferably 5% by mass or less, more preferably 3% by mass or less, and even more preferably 1.5% by mass or less, relative to 100% by mass of the non-volatile components of the resin composition.
[0116] When the resin composition contains (E) polymeric resin, the content of (E) component in the resin composition is preferably 1% by mass or more, more preferably 2% by mass or more, further preferably 3% by mass or more, and preferably 10% by mass or less, more preferably 7% by mass or less, and further preferably 4% by mass or less, relative to 100% by mass of the resin component in the resin composition.
[0117] <(F) Optional Additives> The resin composition of the present invention may, as an optional component, further comprise (F) optional additives. The (F) optional additives do not include components belonging to (A) through (E) above. Examples of (F) optional additives include organometallic compounds such as organocopper compounds, organozinc compounds, and organocobalt compounds; colorants such as phthalocyanine blue, phthalocyanine green, iodine green, diazo yellow, crystal violet, titanium dioxide, and carbon black; polymerization inhibitors such as hydroquinone, catechol, pyrogallol, and phenothiazine; leveling agents such as silicone-based leveling agents and acrylic polymer-based leveling agents; thickeners such as BENTON and montmorillonite; defoamers such as silicone-based defoamers, acrylic defoamers, fluorinated defoamers, and vinyl resin-based defoamers; ultraviolet absorbers such as benzotriazole-based ultraviolet absorbers; adhesion promoters such as triazole-based, tetraazole-based, and triazine-based adhesion promoters; and hindered phenolic antioxidants. Antioxidants such as bis(phenylene) derivatives; fluorescent whitening agents such as diphenylethylene derivatives; surfactants such as fluorinated surfactants and organosilicon surfactants; flame retardants such as phosphorus-based flame retardants (e.g., phosphate ester compounds, phosphazene compounds, phosphonic acid compounds, red phosphorus), nitrogen-based flame retardants (e.g., melamine sulfate), halogen-based flame retardants, and inorganic flame retardants (e.g., antimony trioxide); dispersants such as phosphate ester dispersants, polyoxyalkylene dispersants, acetylene dispersants, organosilicon dispersants, anionic dispersants, and cationic dispersants; stabilizers such as borate ester stabilizers, titanate stabilizers, aluminate stabilizers, zirconate stabilizers, isocyanate stabilizers, carboxylic acid stabilizers, and carboxylic anhydride stabilizers. (F) Optional additives may be used alone or in combination of two or more.
[0118] <(G) solvent> The resin composition may further include, in combination with the non-volatile components (A) to (F) above, a solvent (G) as an optional volatile component. As the solvent (G), an organic solvent may be used, for example. Examples of organic solvents include ketone solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; ester solvents such as methyl acetate, ethyl acetate, butyl acetate, isobutyl acetate, isoamyl acetate, methyl propionate, ethyl propionate, and γ-butyrolactone; ether solvents such as tetrahydropyran, tetrahydrofuran, 1,4-dioxane, diethyl ether, diisopropyl ether, dibutyl ether, diphenyl ether, and anisole; alcohol solvents such as methanol, ethanol, propanol, butanol, and ethylene glycol; and 2-ethoxyethyl acetate, propylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, ethyl diethylene glycol acetate, γ-butyrolactone, and methoxypropyl ether. Ether ester solvents such as methyl lactate; ester alcohol solvents such as methyl lactate, ethyl lactate, and methyl 2-hydroxyisobutyrate; ether alcohol solvents such as 2-methoxypropanol, 2-methoxyethanol, 2-ethoxyethanol, propylene glycol monomethyl ether, and diethylene glycol monobutyl ether (butyl carbitol); amide solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone; sulfoxide solvents such as dimethyl sulfoxide; nitrile solvents such as acetonitrile and propionitrile; aliphatic hydrocarbon solvents such as hexane, cyclopentane, cyclohexane, and methylcyclohexane; and aromatic hydrocarbon solvents such as benzene, toluene, xylene, ethylbenzene, and trimethylbenzene. (G) One solvent may be used alone, or two or more solvents may be used in combination.
[0119] The content of (G) solvent in the resin composition relative to 100% by mass of all components of the resin composition can be, for example, 60% by mass or less, 40% by mass or less, 30% by mass or less, 20% by mass or less, 15% by mass or less, or 10% by mass or less. Alternatively, the content of (G) solvent in the resin composition can be 0% by mass.
[0120] From the viewpoint of further maximizing the desired effects of the present invention, the resin composition contains little or no epoxy resin. The epoxy resin content in the resin composition is preferably 3% by mass or less relative to 100% by mass of the resin component of the resin composition, more preferably 2% by mass or less, and even more preferably 1% by mass or less, 0.5% by mass or less, 0.3% by mass or less, 0.1% by mass or less, or 0.05% by mass or less. The lower limit of this epoxy resin content can be 0% by mass or greater than 0% by mass; from the viewpoint of further maximizing the desired effects of the present invention, the closer to 0% by mass, the more preferred, and even more preferably 0% by mass.
[0121] From the viewpoint of further maximizing the desired effects of the present invention, the resin composition contains little or no thermosetting resin selected from the group consisting of active ester resins, phenolic resins, cyanate ester resins, benzoxazine resins, carbodiimide resins, acid anhydride resins, amine resins, and thiol resins. Since active ester resins, phenolic resins, cyanate ester resins, benzoxazine resins, carbodiimide resins, acid anhydride resins, amine resins, and thiol resins can react with epoxy resins and function as curing agents, these thermosetting resins are sometimes collectively referred to as "epoxy resin curing agents." The content of epoxy resin curing agent in the resin composition is preferably 3% by mass or less, more preferably 2% by mass or less, and even more preferably 1% by mass or less, 0.5% by mass or less, 0.3% by mass or less, 0.1% by mass or less, or 0.05% by mass or less, relative to 100% by mass of the resin component of the resin composition. The lower limit of the content of the epoxy resin curing agent can be 0% by mass or greater than 0% by mass. From the viewpoint of further maximizing the desired effect of the present invention, it is more preferable to be closer to 0% by mass, and even more preferably 0% by mass.
[0122] [Method for manufacturing the resin composition] The resin composition can be manufactured, for example, by mixing components that may be included in the resin composition. Thus, the resin composition can be manufactured by a manufacturing method comprising the steps of mixing (A) a high molecular weight, low-elasticity compound having free radical polymerizable groups at the ends, (B) an inorganic filler, and (C) a compound having free radical polymerizable groups. This manufacturing method optionally includes the step of mixing optional components such as components (D) through (G). Components (A) through (G) can be mixed partially or entirely simultaneously, or they can be mixed sequentially.
[0123] [Characteristics of the Resin Composition] The resin composition of the present invention comprises components (A), (B), and (C) (and, as needed, components (D), (E), (F), and (G)), thus enabling the production of cured products with low dielectric loss tangent, the ability to suppress warping after curing, and excellent reflow soldering resistance.
[0124] The cured resin composition of the present invention exhibits a low dielectric loss tangent. Therefore, an insulating layer with a low dielectric loss tangent is achieved based on this cured product. For example, as described later in the section <Experimental Example 1: Test for Determination of Dielectric Loss Tangent Df>, when the test was conducted at 5.8 GHz and 23°C, the dielectric loss tangent of the cured product obtained by heat-curing the resin composition (layer) at 190°C for 90 minutes is preferably 0.0035 or less, more preferably 0.0032 or less, and even more preferably 0.003 or less. The lower limit value of the dielectric loss tangent can be set to 0.0001 or more, etc.
[0125] The cured resin composition of the present invention can effectively suppress warping after curing. For example, when measuring the warping after curing as described in the section "Experimental Example 2: Warping Measurement Test" below, the warping of the cured product obtained by heating the resin composition (layer) at 100°C for 30 minutes and then at 200°C for 90 minutes is preferably less than 2,500, more preferably less than 2,200, and even more preferably less than 2,000. In the cured resin composition (layer), the lower limit value of the warping after curing can be set to 100 or more, etc.
[0126] The cured resin composition of the present invention can effectively suppress the occurrence of abnormalities such as expansion after reflow soldering. Therefore, the resin composition of the present invention can achieve an insulating layer with excellent reflow soldering resistance. For example, on an insulating layer formed by heat curing the resin composition (layer) at 200°C for 90 minutes, a conductor layer is formed by laminating metal foil to obtain five 100mm × 50mm test pieces. Furthermore, these test pieces are fed 10 times into a reflow soldering apparatus that reproduces a solder reflow temperature of 260°C (reflow soldering temperature profile based on IPC / JEDEC J-STD-020C). In this case, the number of test pieces exhibiting abnormalities such as expansion is preferably one or less, more preferably zero. A specific method for evaluating reflow soldering resistance can be adopted as described in <Experimental Example 3: Evaluation Test of Reflow Soldering Resistance> described later.
[0127] The resin composition of the present invention can achieve a resin composition layer with excellent appearance. Therefore, when forming a resin composition layer using the resin composition of the present invention, unevenness and pinholes in the resin composition layer can be suppressed. For example, when forming a resin composition layer by coating, it is preferable to stop until unevenness and pinholes occur in a portion of the resin composition layer, and more preferably, the entire resin composition layer does not experience unevenness and pinholes. The method for evaluating the appearance of the resin composition layer can be, for example, the method described in <Experimental Example 4: Evaluation of the Appearance of the Resin Composition Layer>.
[0128] [Uses of the resin composition] As described above, the resin composition of the present invention can produce cured products with low dielectric loss tangent, suppression of warpage after curing, and excellent reflow soldering resistance. Therefore, the resin composition of the present invention is suitable for use as a resin composition for forming an insulating layer of a printed circuit board (resin composition for insulating layer of printed circuit board), and more suitable for use as a resin composition for forming an interlayer insulating layer of a printed circuit board (resin composition for interlayer insulating layer of printed circuit board). Furthermore, the resin composition of the present invention is also suitable for use as a resin composition for forming an insulating layer of a redistribution substrate of a semiconductor package (resin composition for insulating layer of redistribution substrate). It should be noted that, in the present invention, printed circuit boards and redistribution substrates are collectively referred to as "circuit boards," therefore, the resin composition of the present invention is suitable for use as an insulating layer of a circuit board.
[0129] The resin composition of the present invention can be further widely used in applications requiring resin compositions, such as resin sheets, prepregs and other sheet-like laminated materials, solder resists, underfill materials, chip bonding materials, through-hole filling resins, sealing resins, and component embedding resins.
[0130] [Laminated sheet materials (resin sheets, prepregs)] The resin composition of the present invention can be used directly or in the form of a sheet-like laminate containing the resin composition.
[0131] As a sheet-like laminated material, resin sheets and prepregs as shown below are preferred.
[0132] In one embodiment, the resin sheet is characterized in that it comprises a support and a layer of resin composition disposed on the support (hereinafter referred to as "resin composition layer"), the resin composition layer being formed of the resin composition of the present invention.
[0133] The suitable thickness of the resin composition layer varies depending on the application and can be appropriately determined according to the application. For example, from the viewpoint of thinning printed circuit boards and semiconductor packages, the thickness of the resin composition layer is preferably 100 μm or less, 80 μm or less, 60 μm or less, 50 μm or less, 40 μm or less, or 30 μm or less. There is no particular limitation on the lower limit of the resin composition layer thickness, and it can usually be set to 1 μm or more, 5 μm or more, etc.
[0134] Examples of supports include thermoplastic resin films, metal foils, and release paper, with thermoplastic resin films and metal foils being preferred. Therefore, in a suitable embodiment, the support is a thermoplastic resin film or a metal foil.
[0135] When using a thermoplastic resin film as a support, examples of thermoplastic resins include polyesters such as polyethylene terephthalate (PET) and polyethylene naphthalate (PEN); acrylics such as polycarbonate (PC) and polymethyl methacrylate (PMMA); cyclic polyolefins, cellulose triacetate (TAC), polyether sulfide (PES), polyetherketone, and polyimide. Among these, polyethylene terephthalate and polyethylene naphthalate are preferred, and inexpensive polyethylene terephthalate is particularly preferred.
[0136] When using metal foil as a support, examples of metal foil include copper foil and aluminum foil, with copper foil being preferred. Copper foil can be used as the support, either as a single metal of copper or as an alloy of copper with other metals (e.g., tin, chromium, silver, magnesium, nickel, zirconium, silicon, titanium, etc.).
[0137] The surface of the support that bonds to the resin composition layer can be treated with matte finish, corona treatment, or antistatic treatment. Furthermore, a support with a release layer can be used as the support, on the surface bonding to the resin composition layer. The release agent used in the release layer of the support with the release layer can be, for example, one or more release agents selected from alkyd resins, polyolefin resins, polyurethane resins, and silicone resins. Commercially available release agents include, for example, alkyd resin-based release agents such as "SK-1," "AL-5," and "AL-7" manufactured by Lintec Corporation. In addition, commercially available products that serve as supports with release layers include, for example, LINTEC's "SK-1", "AL-5", and "AL-7" PET films with release layers made primarily of alkyd resin-based release agents; Toray's "LumirrorT60"; Teijin's "Purex"; and Unipul's "Unipul".
[0138] The thickness of the support is not particularly limited, but is preferably in the range of 5μm to 75μm, and more preferably in the range of 10μm to 60μm. It should be noted that when using a support with a release layer, the overall thickness of the support with the release layer is preferably within the above range.
[0139] When using a metal foil as a support, a metal foil with a support substrate can be obtained by bonding a peelable support substrate onto a thin metal foil. In one embodiment, the metal foil with a support substrate includes a support substrate, a release layer disposed on the support substrate, and a metal foil disposed on the release layer. When using a metal foil with a support substrate as a support, a resin composition layer is disposed on the metal foil.
[0140] In metal foils with a support substrate, the material of the support substrate is not particularly limited, and examples include copper foil, aluminum foil, stainless steel foil, titanium foil, and copper alloy foil. When copper foil is used as the support substrate, it can be electrolytic copper foil or rolled copper foil. Furthermore, the release layer is not particularly limited as long as it can peel the metal foil off the support substrate, and examples include alloy layers selected from elements such as Cr, Ni, Co, Fe, Mo, Ti, W, and P; organic coatings, etc.
[0141] In a metal foil with a supporting substrate, the preferred material for the metal foil is, for example, copper foil or copper alloy foil.
[0142] In the metal foil with a supporting substrate, the thickness of the supporting substrate is not particularly limited, but is preferably in the range of 10 μm to 150 μm, and more preferably in the range of 10 μm to 100 μm. Alternatively, the thickness of the metal foil can be set to, for example, in the range of 0.1 μm to 10 μm.
[0143] In one embodiment, the resin sheet may further comprise any layer as needed. Examples of such arbitrary layers include, for instance, a protective film disposed on the side of the resin composition layer that is not bonded to the support (i.e., the side opposite to the support). The thickness of the protective film is not particularly limited, and is, for example, 1 μm to 40 μm. By laminating the protective film, the adhesion and damage of contaminants and the like on the surface of the resin composition layer can be suppressed.
[0144] Resin sheets can be manufactured by, for example, by directly applying a liquid resin composition onto a support using a die coater or similar tool, or by preparing a resin varnish containing a resin composition dissolved in an organic solvent, applying it onto a support, and then drying it to form a resin composition layer.
[0145] As organic solvents, the same solvents described as components of the resin composition can be listed. One organic solvent may be used alone, or two or more may be used in combination.
[0146] Drying can be carried out by known methods such as heating or blowing hot air. Drying conditions are not particularly limited, but drying is performed such that the content of organic solvent in the resin composition layer is 10% by mass or less, preferably 5% by mass or less. The drying method also varies depending on the boiling point of the organic solvent in the resin composition or resin varnish. For example, when using a resin composition or resin varnish containing 30% to 60% by mass of organic solvent, a resin composition layer can be formed by drying at 50°C to 150°C for 3 to 10 minutes.
[0147] The resin sheets can be stored in rolls. When the resin sheet has a protective film, it can be used by peeling off the protective film.
[0148] In one embodiment, the prepreg is formed by impregnating the resin composition of the present invention into a sheet fiber substrate.
[0149] The sheet fiber substrate used in the prepreg is not particularly limited, and commonly used substrates such as glass cloth, aramid nonwoven fabric, and liquid crystal polymer nonwoven fabric can be used. From the viewpoint of thinning printed circuit boards and semiconductor chip packages, the thickness of the sheet fiber substrate is preferably 50 μm or less, more preferably 40 μm or less, further preferably 30 μm or less, and particularly preferably 20 μm or less. There is no particular limitation on the lower limit of the sheet fiber substrate thickness. The lower limit of the sheet fiber substrate thickness is typically 10 μm or more.
[0150] Prepregs can be manufactured using known methods such as hot-melt methods and solvent methods.
[0151] The thickness of the prepreg can be set to the same range as the resin composition layer in the resin sheet described above.
[0152] The sheet-like laminate material of the present invention is suitable for forming an insulating layer of a printed circuit board (for use as an insulating layer of a printed circuit board), and is more suitable for forming an interlayer insulating layer of a printed circuit board (for use as an interlayer insulating layer of a printed circuit board). Additionally, the sheet-like laminate material of the present invention is suitable for forming an insulating layer of a redistribution substrate of a semiconductor package (for use as an insulating layer of a redistribution substrate). That is, the sheet-like laminate material of the present invention is suitable for use as an insulating layer of a circuit board.
[0153] [Circuit board] The resin composition of the present invention can be used to form an insulating layer of a circuit board. The present invention also provides such a circuit board, i.e., a circuit board comprising an insulating layer, said insulating layer comprising a cured product of the resin composition of the present invention.
[0154] Printed Circuit Boards In one embodiment, the circuit board of the present invention is a printed circuit board.
[0155] Printed circuit boards can be manufactured, for example, using the aforementioned resin sheet and by a method including the processes described in (I) and (II) below.
[0156] (I) A process of laminating a resin sheet onto an inner substrate in such a way that the resin composition layer of the resin sheet is bonded to the inner substrate. (II) The process of curing (e.g., thermosetting) a resin composition layer to form an insulating layer.
[0157] The "inner layer substrate" used in process (I) refers to the component that forms the substrate of the printed circuit board, such as glass epoxy substrate, metal substrate, polyester substrate, polyimide substrate, BT resin substrate, thermosetting polyphenylene ether substrate, etc. Furthermore, this substrate may have a conductive layer on one or both sides, and this conductive layer may be patterned. Sometimes, an inner layer substrate with a conductive layer (circuit) formed on one or both sides of the substrate is referred to as an "inner layer circuit substrate." Additionally, intermediate manufactured parts that should be further formed with insulating layers and / or conductive layers during the manufacturing of the printed circuit board are also included in the "inner layer substrate" mentioned in this invention. When the printed circuit board is a component-integrated circuit board, an inner layer substrate with built-in components can be used.
[0158] The lamination of the inner substrate and the resin sheet can be achieved, for example, by heating and pressing the resin sheet onto the inner substrate from the support side. Examples of components for heating and pressing the resin sheet onto the inner substrate (hereinafter also referred to as "heat-pressing components") include, for example, heated metal plates (SUS mirror plates, etc.) or metal rollers (SUS rollers). It should be noted that the heat-pressing components can be applied directly to the resin sheet, or pressure can be applied through an elastic material such as heat-resistant rubber, so that the resin sheet fully follows the surface irregularities of the inner substrate.
[0159] The lamination of the inner substrate and the resin sheet can be performed by vacuum lamination. In vacuum lamination, the heating and pressing temperature is preferably in the range of 60°C to 160°C, more preferably 80°C to 140°C; the heating and pressing pressure is preferably in the range of 0.098 MPa to 1.77 MPa, more preferably 0.29 MPa to 1.47 MPa; and the heating and pressing time is preferably in the range of 20 seconds to 400 seconds, more preferably 30 seconds to 300 seconds. Lamination is preferably performed under reduced pressure conditions of 26.7 hPa or less.
[0160] Lamination can be performed using commercially available vacuum laminators. Examples of commercially available vacuum laminators include, for instance, the vacuum pressure laminator manufactured by Meiki Seisakusho, the vacuum applicator manufactured by Nikko-Materials, and intermittent vacuum pressure laminators.
[0161] After lamination, the laminated resin sheets can be smoothed by applying pressure to the heated pressing members under normal pressure (atmospheric pressure), for example, from the support side. The pressure conditions for smoothing can be set to the same conditions as the heated pressing conditions for lamination described above. The smoothing process can be performed using a commercially available laminator. It should be noted that lamination and smoothing can be performed continuously using the aforementioned commercially available vacuum laminator.
[0162] The support can be removed between steps (I) and (II), or after step (II). It should be noted that when using a metal foil as the support, the metal foil can be used to form the conductor layer without peeling off the support. Alternatively, when using a metal foil with a support substrate as the support, only the support substrate (and release layer) need to be peeled off. Furthermore, the metal foil can be used to form the conductor layer.
[0163] In step (II), the resin composition layer is cured (e.g., thermocure) to form an insulating layer containing the cured resin composition. The curing conditions for the resin composition layer are not particularly limited, and conditions typically used when forming insulating layers for printed circuit boards can be used.
[0164] For example, the thermosetting conditions of the resin composition layer vary depending on the type of resin composition, etc. In one embodiment, the curing temperature is preferably 140°C to 250°C, more preferably 150°C to 240°C, and even more preferably 160°C to 230°C. The curing time is preferably 5 minutes to 240 minutes, more preferably 10 minutes to 150 minutes, and even more preferably 15 minutes to 120 minutes.
[0165] Before heat curing the resin composition layer, the resin composition layer can be preheated at a temperature below the curing temperature. For example, before heat curing the resin composition layer, the resin composition layer can be preheated at a temperature of 50°C to 140°C, preferably 60°C to 135°C, more preferably 70°C to 130°C for at least 5 minutes, preferably 5 minutes to 150 minutes, more preferably 15 minutes to 120 minutes, and even more preferably 15 minutes to 100 minutes.
[0166] In manufacturing a printed circuit board, steps (III) of creating openings in the insulating layer, (IV) of roughening the insulating layer, and (V) of forming a conductor layer can be further performed. These steps (III) to (V) can be performed according to various methods known to those skilled in the art for manufacturing printed circuit boards. It should be noted that when removing the support after step (II), the removal of the support can be performed between steps (II) and (III), between steps (III) and (IV), or between steps (IV) and (V). In addition, the formation of the insulating and conductor layers in steps (I) to (V) can be repeated as needed to form a multilayer wiring board.
[0167] In other embodiments, the printed circuit board of the present invention can be manufactured using the prepreg described above. The manufacturing method is basically the same as that used when using resin sheets.
[0168] Step (III) is the process of creating openings in the insulating layer, thereby forming vias, through holes, etc., within the insulating layer. Step (III) can be performed using tools such as drills, lasers, or plasma, depending on the composition of the resin composition used to form the insulating layer. The size and shape of the holes can be appropriately determined according to the design of the printed circuit board.
[0169] Process (IV) is a process for roughening the insulating layer. Typically, smear removal is also performed in this process (IV). The steps and conditions for roughening are not particularly limited; known steps and conditions commonly used in forming the insulating layer of a printed circuit board can be employed. For example, the insulating layer can be roughened sequentially by performing a swelling treatment based on a swelling solution, a roughening treatment based on an oxidizing agent, and a neutralization treatment based on a neutralizing solution.
[0170] The swelling solution used in the roughening treatment is not particularly limited, and examples include alkaline solutions and surfactant solutions, with an alkaline solution being preferred, and sodium hydroxide solution or potassium hydroxide solution being more preferred. Commercially available swelling solutions include, for example, "Swelling Dip Securiganth P" and "Swelling Dip Securiganth SBU" manufactured by Atotech Japan. The swelling treatment based on the swelling solution is not particularly limited, and can be performed, for example, by immersing the insulating layer in a swelling solution at 30°C to 90°C for 1 to 20 minutes. From the viewpoint of suppressing the resin swelling of the insulating layer to an appropriate level, it is preferable to immerse the insulating layer in a swelling solution at 40°C to 80°C for 5 to 15 minutes.
[0171] The oxidant used in the roughening treatment is not particularly limited, and examples include, for instance, an alkaline permanganate solution in which potassium permanganate or sodium permanganate is dissolved in an aqueous solution of sodium hydroxide. Roughening treatment based on an oxidant such as an alkaline permanganate solution is preferably performed by immersing the insulating layer in an oxidant solution heated to 60°C to 100°C for 10 to 30 minutes. Furthermore, the concentration of permanganate in the alkaline permanganate solution is preferably 5% to 10% by mass. Commercially available oxidants include, for example, alkaline permanganate solutions such as "Concentrate Compact CP," "Concentrate Compact P," and "Dosing Solution Securiganth P" manufactured by Atotech Japan.
[0172] Furthermore, the neutralizing liquid used in the roughening process is preferably an acidic aqueous solution, and commercially available products include, for example, "Reduction Solution Securiganth P" manufactured by Atotech Japan.
[0173] Treatment based on the neutralizing solution can be performed by immersing the roughened surface treated with an oxidant in a neutralizing solution at 30°C to 80°C for 5 to 30 minutes. From the viewpoint of workability, it is preferable to immerse the roughened object treated with an oxidant in a neutralizing solution at 40°C to 70°C for 5 to 20 minutes.
[0174] Step (V) is the step of forming a conductor layer, which is formed on the insulating layer. The conductor material used in the conductor layer is not particularly limited. In a suitable embodiment, the conductor layer comprises one or more metals selected from the group consisting of gold, platinum, palladium, silver, copper, aluminum, cobalt, chromium, zinc, nickel, titanium, tungsten, iron, tin, and indium. The conductor layer can be a single metal layer or an alloy layer. Examples of alloy layers include layers formed from alloys of two or more metals selected from the above group (e.g., nickel-chromium alloy, copper-nickel alloy, and copper-titanium alloy). From the viewpoints of versatility, cost, and ease of patterning in conductor layer formation, a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper is preferred; or an alloy layer of nickel-chromium alloy, copper-nickel alloy, or copper-titanium alloy; more preferably, a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper; or an alloy layer of nickel-chromium alloy; and even more preferably, a single metal layer of copper.
[0175] The conductor layer can be a single-layer structure or a multi-layer structure obtained by stacking two or more single-metal layers or alloy layers formed of different kinds of metals or alloys. When the conductor layer is a multi-layer structure, the layer in contact with the insulating layer is preferably a single-metal layer of chromium, zinc or titanium or an alloy layer of nickel-chromium alloy.
[0176] The thickness of the conductor layer depends on the desired printed circuit board design, typically 3μm to 35μm, preferably 5μm to 30μm.
[0177] The conductor layer can be formed using metal foil. When using metal foil to form the conductor layer, step (V) is suitable to be performed between steps (I) and (II). For example, after step (I), the support is removed, and metal foil is laminated onto the surface of the exposed resin composition layer. The lamination of the resin composition layer and the metal foil can be performed using vacuum lamination. The lamination conditions can be set to the same conditions described for step (I). Next, step (II) is performed to form an insulating layer. Subsequently, using the metal foil on the insulating layer, a conductor layer with a desired wiring pattern can be formed using existing known techniques such as a modified semi-additive method.
[0178] Metal foil can be manufactured using known methods such as electrolysis and rolling. Commercially available metal foils include, for example, HLP foil and JXUT-III foil manufactured by JX Metals Corporation, and 3EC-III foil and TP-III foil manufactured by Mitsui Metals & Mining Corporation.
[0179] Alternatively, when using a metal foil, or a metal foil with a supporting substrate, as a support for the resin sheet, the metal foil can be used to form a conductor layer, as described above.
[0180] In other embodiments, the conductor layer can be formed by plating. From the viewpoint of facilitating the formation of fine wiring, when the conductor layer is formed by plating, it is preferable to form it by a semi-additive method. Hereinafter, examples of forming the conductor layer by a semi-additive method are shown.
[0181] First, a seed plating layer is formed on the surface of an insulating layer using electroless plating. Next, a mask pattern is formed on the seed plating layer, exposing a portion of the seed plating layer corresponding to the desired wiring pattern. After forming a metal layer on the exposed seed plating layer using electrolytic plating, the mask pattern is removed. Subsequently, the unwanted seed plating layer is removed by etching or the like, thus forming a conductor layer with the desired wiring pattern.
[0182] <Rewiring substrate for semiconductor packages> In one embodiment, the circuit board of the present invention is a redistribution substrate (redistribution layer) of a semiconductor package. Hereinafter, a method for manufacturing a semiconductor package will be described.
[0183] In a semiconductor package, the insulating layer serving as a redistribution substrate comprises: an insulating layer containing a cured resin composition of the present invention. It should be noted that the semiconductor package may include a sealing layer containing a cured resin composition of the present invention.
[0184] Semiconductor packages can be manufactured, for example, using the resin composition and resin sheet of the present invention, and by a method including the steps (1) to (6) described below. To form the redistribution layer (an insulating layer for forming the redistribution substrate) of step (5) or the sealing layer of step (3), only the resin composition and resin sheet of the present invention need to be used. Hereinafter, an example of forming the redistribution layer and sealing layer using the resin composition and resin sheet is shown. The techniques for forming the redistribution layer and sealing layer of a semiconductor package are well known, and anyone skilled in the art can use the resin composition and resin sheet of the present invention to manufacture a semiconductor package according to known techniques.
[0185] (1) The process of laminating a temporary fixing film on a substrate; (2) The process of temporarily fixing the semiconductor chip onto the temporary fixing film; (3) The process of forming a sealing layer on a semiconductor chip; (4) The process of peeling the substrate and temporary fixing film off the semiconductor chip; (5) A process of forming a rewiring layer as an insulating layer on the surface of a semiconductor chip after the substrate and temporary fixing film have been peeled off; and (6) The process of forming a redistribution layer as a conductor layer on the redistribution forming layer.
[0186] -Process (1)- There are no particular limitations on the materials used in the substrate. Examples of substrates include semiconductor wafers such as silicon wafers; glass wafers; glass substrates; metal substrates such as copper, titanium, stainless steel, and cold-rolled steel sheets (SPCC); substrates in which epoxy resin or the like is impregnated into glass fibers and subjected to thermosetting treatment (e.g., FR-4 substrates); and substrates containing bismaleimide triazine resin (BT resin), etc.
[0187] The material of the temporary fixing film is not particularly limited as long as it can be peeled off from the semiconductor chip in process (4) and can temporarily fix the semiconductor chip. Commercially available products can be used for the temporary fixing film. Examples of commercially available products include REVALPHA manufactured by Nitto Denko Corporation.
[0188] -Process (2)- Temporary fixation of semiconductor chips can be performed using known devices such as flip chip bonding machines and chip bonding machines. The arrangement and number of semiconductor chips can be appropriately set according to the shape and size of the temporary fixation film and the production quantity of the target semiconductor package. For example, they can be arranged into a matrix of rows and columns and temporarily fixed.
[0189] -Process (3)- The resin composition of the resin sheet of the present invention is laminated onto a semiconductor chip, or the resin composition of the present invention is coated onto a semiconductor chip and cured (e.g., thermosetting) to form a sealing layer.
[0190] For example, the stacking of a semiconductor chip and a resin sheet can be performed by heating and pressing the resin sheet onto the semiconductor chip from the support side after removing the protective film from the resin sheet. Examples of components for heating and pressing the resin sheet onto the semiconductor chip (hereinafter also referred to as "heat-pressing components") include, for example, heated metal plates (SUS mirror plates, etc.) or metal rollers (SUS rollers). It should be noted that instead of directly pressing the resin sheet onto the heat-pressing component, it is preferable to press through an elastic material such as heat-resistant rubber so that the resin sheet fully conforms to the surface irregularities of the semiconductor chip. The stacking of the semiconductor chip and the resin sheet can be carried out by vacuum lamination, with the same stacking conditions and preferred range as those described for printed circuit board manufacturing methods.
[0191] After lamination, the resin composition is thermosetting to form a sealing layer. The thermosetting conditions are the same as those described for the manufacturing method of printed circuit boards.
[0192] The support for the resin sheet can be peeled off after the resin sheet is laminated on the semiconductor chip and thermocured, or the support can be peeled off before the resin sheet is laminated on the semiconductor chip.
[0193] When forming a sealing layer by coating the resin composition of the present invention, the coating conditions are the same as those for forming the resin composition layer described for the resin sheet of the present invention, and preferably within the same range.
[0194] -Process (4)- The method for peeling the substrate and the temporary fixing film can be appropriately modified depending on the material of the temporary fixing film. Examples include heating the temporary fixing film to make it foam (or expand) and then peeling it off, and irradiating the substrate side with ultraviolet light to reduce the adhesive force of the temporary fixing film and then peeling it off.
[0195] In methods that involve heating a temporary fixing film to cause it to foam (or expand) and then peel it off, the heating conditions are typically 100°C to 250°C for 1 to 90 seconds or 5 to 15 minutes. Conversely, in methods that involve irradiating the temporary fixing film with ultraviolet light from the substrate side to reduce its adhesive strength and then peel it off, the ultraviolet irradiation dose is typically 10 mJ / cm². 2 ~1000mJ / cm 2 .
[0196] -Process (5)- Using the resin composition and resin sheet of the present invention, a redistribution layer (insulating layer of redistribution substrate) is formed.
[0197] After forming the redistribution layer, vias can be formed in the redistribution layer to enable interlayer interconnection between the semiconductor chip and the conductor layer described later. The vias can be formed according to the material of the redistribution layer and using known methods.
[0198] -Process (6)- Forming a conductor layer on the redistribution layer can be performed in the same manner as step (V) described for the manufacturing method of a printed circuit board. It should be noted that steps (5) and (6) can be performed repeatedly, alternatingly layering (stacking) the conductor layer (redistribution layer) and the redistribution layer (insulating layer).
[0199] In manufacturing a semiconductor package, the following steps may be performed: (7) forming a solder mask layer on a conductor layer (rewiring layer); (8) forming bumps; and (9) dicing multiple semiconductor packages into individual semiconductor packages for monolithic assembly. These steps may be performed in accordance with various methods known to those skilled in the art for manufacturing semiconductor packages.
[0200] By using the resin composition and resin sheet of the present invention, which can achieve a cured product with low dielectric loss tangent, suppression of warpage after curing, and excellent reflow soldering resistance, a redistribution forming layer (insulating layer) is formed, thereby enabling semiconductor packages, whether fan-in or fan-out, to achieve semiconductor packages with minimal transport losses. In one embodiment, the semiconductor package of the present invention is a fan-out package. The resin composition and resin sheet of the present invention can be used for both fan-out panel-level packages (FOPLP) and fan-out wafer-level packages (FOWLP). In one embodiment, the semiconductor package of the present invention is a fan-out panel-level package (FOPLP) or a fan-out wafer-level package (FOWLP).
[0201] [Semiconductor Devices] The semiconductor device of the present invention comprises a layer of cured material containing the resin composition of the present invention. The semiconductor device of the present invention can be manufactured using the circuit board of the present invention.
[0202] As semiconductor devices, various semiconductor devices supplied to electrical products (such as computers, mobile phones, digital cameras, and televisions) and vehicles (such as motorcycles, automobiles, trams, ships, and aircraft) can be listed. Example
[0203] The following examples illustrate specific embodiments of the present invention. However, the present invention is not limited to these examples. In the following description, unless otherwise specified, "parts" and "%" refer to "parts by mass" and "% by mass," respectively. Furthermore, unless otherwise specified, the temperature and pressure conditions are room temperature (23°C) and atmospheric pressure (1 atm).
[0204] <Synthesis Example 1: Synthesis of Elastomer A1> Add 770.1 g of propylene glycol methyl ether acetate (hereinafter sometimes referred to as "PGMAc"), 67.5 g (0.30 mol) of isophorone diisocyanate (hereinafter sometimes referred to as "IPDI"), 562.6 g (0.15 mol) of OH-terminated polybutadiene ("G-3000", manufactured by Nippon Soda Co., Ltd., Mn: 3,000, hydroxyl value: 30.3 mg KOH / g), 0.28 g of dibutoxybis(ethyl acetoacetate)zirconium ("Orgachix ZC-580", manufactured by Matsumoto Fine Chemical Co., Ltd.), and 0.14 g of zinc complex ("K-KAT XK-614", manufactured by Kusumoto Chemical Co., Ltd.) to a flask equipped with a stirrer, thermometer, and condenser. Heat the mixture to 60°C and maintain this temperature for 4 hours.
[0205] 16.6 g (0.076 mol) of pyromellitic anhydride was added to the mixed solution. The solution was then heated to 140 °C and reacted for 4 hours.
[0206] In the mixed solution, after confirming that the viscosity increase had ended, it was cooled to 120°C. Subsequently, 20.0 g of 2-hydroxyethyl methacrylate (0.15 mol) and 0.37 g of p-methoxyphenol were added, and the reaction was carried out at 120°C for 2 hours.
[0207] Infrared spectroscopy was used to determine the characteristic absorption, confirming the characteristic absorption of the isocyanate group at 2270 cm⁻¹. -1 The absorption peak completely disappeared, and the non-volatile component was adjusted to 45% by mass using PGMAc.
[0208] Through the above operations, elastomer A1 (a solution with 45% by mass of non-volatile components) with methacrylamide groups at the ends was obtained. The weight-average molecular weight (Mw) of elastomer A1, determined by GPC, was 13,000.
[0209] The elastic modulus of the obtained elastomer A1 was determined by the following method.
[0210] A polyethylene terephthalate film (Toray Industries' "Lumirror R80", 38 μm thick, softening point 130°C) was prepared for release treatment using an alkyd resin-based release agent (Lintec's "AL-5"). Elastomer A1 was uniformly coated onto the support with a dried resin layer thickness of 50 μm using a die-coating machine. The film was then dried in an oven at 10°C / min, increasing the temperature from 70°C to 120°C for a total of 10 minutes, thereby reducing the volatile components to less than 1% by mass relative to the total components of elastomer A1, forming a resin layer of elastomer A1. The dried resin layer was peeled off the support and die-cut into the shape of test piece type 5 as described in JIS K 7127. The elastic modulus was determined by a tensile test based on JIS K 7161 (temperature 25°C, humidity 40%RH, tensile speed 5 mm / min). The elastic modulus of elastomer A1 is 0.02 GPa.
[0211] <Synthesis Example 2: Synthesis of Elastomer A2> Add 727.2 g of PGMAc, 135.9 g (0.61 mol) of IPDI, 459.1 g (0.31 mol) of OH-terminated polybutadiene ("G-1000" manufactured by Nippon Soda Co., Ltd., Mn: 1,400, hydroxyl value: 74.8 mg KOH / g), 0.26 g of dibutoxybis(ethyl acetoacetate)zirconium ("Orgaticx ZC-580" manufactured by Matsumoto Fine Chemical Co., Ltd.), and 0.13 g of zinc complex ("K-KAT XK-614" manufactured by Kusumoto Chemical Co., Ltd.) to a flask equipped with a stirrer, thermometer, and condenser. Heat the mixture to 60°C and maintain this temperature for 4 hours.
[0212] 33.4 g (0.15 mol) of pyromellitic anhydride was added to the mixture. The mixture was then heated to 140 °C and reacted for 4 hours.
[0213] In the mixed solution, after confirming that the viscosity increase had ended, it was cooled to 120°C. Subsequently, 40.2 g of 2-hydroxyethyl methacrylate (0.31 mol) and 0.34 g of p-methoxyphenol were added, and the reaction was carried out at 120°C for 2 hours.
[0214] Infrared spectroscopy was used to determine the characteristic absorption, confirming the characteristic absorption of the isocyanate group at 2270 cm⁻¹. -1 The absorption peak completely disappeared, and the non-volatile component was adjusted to 45% by mass using PGMAc.
[0215] Through the above operations, elastomer A2 (a solution with 45% by mass of non-volatile components) with methacryloyl groups at the ends was synthesized. The weight-average molecular weight (Mw) of elastomer A2, determined by GPC, was 22,000.
[0216] The elastic modulus of elastomer A2 was determined using the same procedure as for elastomer A1. The elastic modulus of elastomer A2 was 0.01 GPa.
[0217] <Synthesis Example 3: Synthesis of Elastomer A3> Add 727.2 g of PGMAc, 135.9 g (0.61 mol) of IPDI, 459.1 g (0.31 mol) of OH-terminated polybutadiene (Nippon Soda Co., Ltd.'s "G-1000"), 0.26 g of tetraacetylacetone zirconium (Matsumoto Fine Chemical Co., Ltd.'s "Orgaticx ZC-150"), and 0.13 g of diisopropoxybis(ethyl acetoacetate)titanium (Matsumoto Fine Chemical Co., Ltd.'s "Orgaticx TC-750") to a flask equipped with a stirrer, thermometer, and condenser. Heat the mixture to 60°C and maintain that temperature for 4 hours.
[0218] 49.3 g (0.15 mol) of benzophenone tetracarboxylic acid dianhydride was added to the mixed solution. The solution was then heated to 140 °C and reacted for 4 hours.
[0219] In the mixed solution, after confirming that the viscosity increase had ended, it was cooled to 120°C. Subsequently, 34.8 g of 2-hydroxyethyl acrylate (0.30 mol) and 0.34 g of p-methoxyphenol were added, and the reaction was carried out at 120°C for 2 hours.
[0220] Infrared spectroscopy was used to determine the characteristic absorption, confirming the characteristic absorption of the isocyanate group at 2270 cm⁻¹. -1 The absorption peak completely disappeared. Next, using PGMAc, the reactants were adjusted to a non-volatile content of 45% by mass. Following the above procedure, elastomer A3 (a solution with a non-volatile content of 45% by mass) with acryloyl groups at the ends was obtained. The weight-average molecular weight (Mw) of elastomer A3, determined by GPC, was 16,000.
[0221] The elastic modulus of elastomer A3 was determined using the same procedure as for elastomer A1. The elastic modulus of elastomer A3 was 0.05 GPa.
[0222] <Synthesis Example 4: Synthesis of Elastomer A4> Add 770.1 g of PGMAc, 67.5 g (0.30 mol) of IPDI, 300.0 g (0.15 mol) of polycarbonate diol (Kuraray Co., Ltd.'s "C-2015N", Mn: approx. 2000, hydroxyl equivalent: 1000 g / eq.), 0.28 g of dibutoxybis(ethyl acetoacetate)zirconium (Matsumoto Fine Chemical Co., Ltd.'s "Orgaticx ZC-580"), and 0.14 g of zinc complex (Kuzumoto Chemical Co., Ltd.'s "K-KAT XK-614"). Heat the mixture to 60°C and maintain that temperature for 4 hours.
[0223] 16.6 g (0.076 mol) of pyromellitic anhydride was added to the mixed solution. The solution was then heated to 140 °C and reacted for 4 hours.
[0224] In the mixed solution, after confirming that the viscosity increase had ended, it was cooled to 120°C. Subsequently, 20.0 g of 2-hydroxyethyl methacrylate (0.15 mol) and 0.37 g of p-methoxyphenol were added, and the reaction was carried out at 120°C for 2 hours.
[0225] Infrared spectroscopy was used to determine the characteristic absorption, confirming that the characteristic absorption of the isocyanate group, i.e., the absorption peak at 2270 cm⁻¹, had completely disappeared. PGMAc was used to adjust the non-volatile component to 45% by mass.
[0226] Through the above operations, elastomer A4 (a solution with 45% by mass of non-volatile components) with methacrylamide groups at the ends was obtained. The weight-average molecular weight (Mw) of elastomer A4, determined by GPC, was 150,000.
[0227] The elastic modulus of elastomer A4 was determined using the same procedure as for elastomer A1. The elastic modulus of elastomer A4 was 0.05 GPa.
[0228] <Synthesis Example 5: Synthesis of Elastomer A5> 69g of OH-terminated polybutadiene ("G-3000" manufactured by Nippon Soda Co., Ltd.), 40g of propylene glycol monomethyl ether acetate ("PGMEA" manufactured by Resonac Co., Ltd.), and 0.005g of dibutyltin laurate were added to a reaction vessel and mixed until homogeneous. Once homogeneous, the temperature was raised to 60°C, and then 8g of isophorone diisocyanate ("IPDI" manufactured by Evonik Degussa Japan Co., Ltd., isocyanate equivalent: 113g / eq.) was added while stirring, and the reaction was carried out for approximately 3 hours.
[0229] Next, 23 g of cresol phenolic resin (DIC's "KA-1160", hydroxyl equivalent: 117 g / eq.) and 60 g of propylene glycol monomethyl ether acetate (Resonac's "PGMEA") were added to the reactants, and the mixture was refluxed at 150°C with stirring for approximately 10 hours. The reaction was then carried out using FT-IR at 2250 cm⁻¹. -1 The disappearance of the NCO peak was confirmed. The disappearance of the NCO peak was taken as the endpoint of the reaction, and the reactants were cooled to room temperature. The reactants were then filtered through a 100-mesh filter cloth to obtain elastomer A5 (butadiene resin containing phenolic hydroxyl groups: a solution of 50% by mass of non-volatile components) with a butadiene structure and phenolic hydroxyl groups. Elastomer A5 does not have free radical polymerizable groups at the molecular ends. The weight-average molecular weight (Mw) of elastomer A5, determined by GPC, is 27,000.
[0230] The elastic modulus of elastomer A5 was determined using the same procedure as for elastomer A1. The elastic modulus of elastomer A5 was 0.05 GPa.
[0231] <Synthesis Example 6: Synthesis of Vinyl Resin B1> 201 g of o-allylphenol and 1000 g of toluene were added to a reaction vessel, and dissolved while the vessel was purged with nitrogen under reduced pressure. Next, 152 g of isophthaloyl chloride was added and dissolved. While purging the vessel with nitrogen, 309 g of a 20% sodium hydroxide aqueous solution was added dropwise over 3 hours. The temperature of the system was maintained below 60°C. The mixture was then stirred for 1 hour to allow the reaction to proceed. After the reaction was complete, the reactants were separated to remove the aqueous layer. This process was repeated until the pH of the aqueous layer reached 7. Toluene and other components were then distilled off under reduced pressure to obtain vinyl resin B1. The unsaturated bond equivalent of the obtained vinyl resin B1, calculated based on the feed ratio, was 199 g / eq.
[0232] <Synthesis Example 7: Synthesis of Vinyl Resin B2> 165 g of a dicyclopentadiene-phenol addition polymerization resin (hydroxyl equivalent: 165 g / eq., softening point: 85 °C), 134 g (1.0 mol) of o-allylphenol, and 1200 g of toluene were added to a flask equipped with a thermometer, dropping funnel, condenser, fractionating tube, and stirrer. The system was then purged with nitrogen under reduced pressure. Next, 203 g (1.0 mol) of isophthaloyl chloride was added, and the system was purged with nitrogen under reduced pressure. 0.6 g of tetrabutylammonium bromide was added, and the system was maintained below 60 °C while purging with nitrogen. 412 g of a 20% sodium hydroxide aqueous solution was added dropwise over 3 hours, and the mixture was stirred for 1 hour after the addition was complete. After the reaction was complete, the aqueous layer was removed by sedimentation. Water was then added to the resulting toluene layer, and the mixture was stirred for 15 minutes. The aqueous layer was then removed by sedimentation. This process was repeated until the pH of the aqueous layer reached 7. Furthermore, by using heat drying to adjust the non-volatile components to 70% by mass, vinyl resin B2, as shown in the following chemical formula, is obtained.
[0233] [Chemistry 8] In the above chemical formulas, 's' are each an independent integer greater than or equal to 0 or 1, and the average value of 'r' calculated based on the feed ratio is 1. Additionally, the dashed lines in the chemical formulas represent structures obtained by reacting isophthaloyl chloride, phenol, and / or o-allylphenol via addition polymerization. The calculated unsaturated bond equivalent of vinyl resin B2 based on the feed ratio is 428 g / eq.
[0234] <Synthesis Example 8: Synthesis of Maleimide Resin B3> A MEK solution (60% by mass) of maleimide resin B3 (Mw / Mn = 1.81, t” = 1.47 (mainly 1, 2 or 3)) to be synthesized by the method described in Synthesis Example 1 of Patent Application Publication No. 2020-500211 of the China Inventions Association. The maleimide resin B3 has the structure shown in the following formula.
[0235] [Chemistry 9] <Examples 1-12, Comparative Examples 1-2: Preparation of Resin Compositions> Weigh each component according to the mass proportions listed in Table 1 below, and further mix 15 parts of MEK (methyl ethyl ketone) and 15 parts of cyclohexanone. Disperse the mixture evenly using a high-speed rotary stirrer to obtain a resin composition (resin varnish). Details of each component listed in Table 1 below are shown below.
[0236] (A) High molecular weight low elasticity compounds with free radical polymerizable groups at the ends (compounds with free radical polymerizable groups at the ends, weight average molecular weight (Mw) greater than 5,000 and less than 300,000, and tensile modulus of elasticity less than 1 GPa as determined by JIS K7161 at 25 °C) • "Elastomer A1": Elastomer A1 obtained in Synthesis Example 1 • "Elastomer A2": Elastomer A2 obtained in Synthesis Example 2 • "Elastomer A3": Elastomer A3 obtained in Synthesis Example 3 • "Elastomer A4": Elastomer A4 obtained in Synthesis Example 4.
[0237] (A') High molecular weight low elasticity compounds that do not have free radical polymerizable groups at the ends (compounds that do not have free radical polymerizable groups at the ends, have a weight-average molecular weight (Mw) greater than 5,000 and less than 300,000, and have a tensile modulus of elasticity of less than 1 GPa as determined by JIS K7161 at 25 °C). • "Elastomer A5": Elastomer A5 obtained in Synthesis Example 5 (B) Inorganic filler materials • "SO-C2": Spherical silica (Admatechs, average particle size 0.5 μm, specific surface area 5.8 m²) surface-treated with an aminosilane-based silane coupling agent (Shin-Etsu Chemical Co., Ltd.'s "KBM-573"). 2 / g) • "Alumina B": Spherical alumina (average particle size of 1.0 μm) that has been surface-treated with an aminosilane coupling agent ("KBM-573" manufactured by Shin-Etsu Chemical Co., Ltd.
[0238] (C) Compounds with free radical polymerizable groups (compounds with free radical polymerizable groups and a weight-average molecular weight (Mw) of less than 5,000) • “OPE-2St 1200”: Vinyl benzyl modified polyphenylene ether (manufactured by Mitsubishi Gas Chemical Co., Ltd., toluene solution with 65% non-volatile components, number average molecular weight (Mn): 1,200) • "BMI-689": Aliphatic maleimide resin (N-alkyl bismaleimide with a backbone derived from dimerized diamine, manufactured by Designer Molecules Inc.) • "BMI-1500": Aliphatic maleimide resin (N-alkyl bismaleimide with a backbone derived from dimerized diamine, manufactured by Designer Molecules Inc.) • “MIR-3000-70MT”: Aromatic maleimide resin (manufactured by Nippon Kayaku Co., Ltd., a MEK / toluene mixed solution with a non-volatile component rate of 70%) • “MIR-5000-60T”: Aromatic maleimide resin (manufactured by Nippon Kayaku Co., Ltd., toluene solution with 60% non-volatile components) • "SA9000": Methacrylic acid modified polyphenylene ether (manufactured by SABIC) • "A-DOG": Dioxanediol diacrylate (manufactured by Shin-Nakamura Chemical Industry Co., Ltd.) • "DAD": diallyl biphenyl ester (manufactured by Nippon Techno Fine Chemical Co., Ltd.) • "DCP": Tricyclodecanediethanol dimethacrylate (manufactured by Shin-Nakamura Chemical Industry Co., Ltd.) • "Petrotack 70": An aliphatic / aromatic copolymer resin with 50% by mass of hydrocarbons with 5 carbon atoms (manufactured by Tosoh Corporation, acrylic resin with an active group equivalent of less than 250 g / eq.). • "Petrotack 90": An aromatic copolymer resin with 30% by mass of 5-carbon hydrocarbons (manufactured by Tosoh Corporation, acrylic resin with an active group equivalent of 250 g / eq. or more). • "HYBRAR5125": A vinyl-containing polystyrene isoprene resin (manufactured by Kuraray Co., Ltd.) • "Vinyl Resin B1": Vinyl Resin B1 obtained in Synthesis Example 6 • "Vinyl Resin B2": Vinyl Resin B2 obtained in Synthesis Example 7 • "Maleimide Resin B3": Maleimide resin B3 obtained in Synthesis Example 8.
[0239] (D) Free radical polymerization initiator • "Luperox DTA": Di-tert-pentyl peroxide (manufactured by Arkema) • "Perbutyl C": Tert-butyl cumyl peroxide (manufactured by Nippon Oil Company).
[0240] (E) Polymer resin • “EXL2655”: Core-shell graft copolymer rubber granules (manufactured by Dow Chemical).
[0241] <Making of Resin Sheets> As a support, a polyethylene terephthalate film (Lumirror R80 manufactured by Toray Industries, with a thickness of 38 μm and a softening point of 130°C) that has undergone mold release treatment using an alkyd resin-based release agent (AL-5 manufactured by LINTEC Corporation) was prepared.
[0242] Using a die coater, the resin compositions obtained in Examples 1-12 and Comparative Examples 1-2 were uniformly coated on the support with a thickness of 50 μm after drying, and dried at 70°C-90°C for 3 minutes, thereby forming a resin composition layer on the support.
[0243] After performing the following test on the resin composition layer (Example 4: Appearance Evaluation of the Resin Composition Layer), a rough surface of a polypropylene film (Alphan MA-411, 15 μm thick, manufactured by Oji F-Tex) was laminated as a protective film onto the surface of the resin composition layer that was not bonded to the support. This resulted in a resin sheet having a support / resin composition layer / protective film in sequence.
[0244] <Experimental Example 1: Determination of Dielectric Loss Tangent Df> The protective film was peeled off from the resin sheet, and the resin composition layer was thermo-cured by heating at 200°C for 90 minutes. The support was then peeled off to obtain the cured product. The cured product was cut into test pieces with a width of 2 mm and a length of 80 mm to obtain evaluation test pieces.
[0245] For this test piece, the dielectric loss tangent (Df value) was measured using a measuring device (HP8362B, Agilent Technologies) and the cavity resonator perturbation method at a measurement frequency of 5.8 GHz and a measurement temperature of 23 °C. Measurements were performed on three test pieces, and the average value was calculated. Based on this average value, the dielectric loss tangent was evaluated according to the following criteria.
[0246] [Evaluation Criteria for Dielectric Loss Tangent Df] “○”: Dielectric loss tangent (Df value) is less than 0.003.
[0247] “△”: The dielectric loss tangent (Df value) is above 0.003 and below 0.0035.
[0248] "×": Dielectric loss tangent (Df value) is greater than 0.0035.
[0249] <Experimental Example 2: Warpage Measurement Test> Using an intermittent vacuum pressure laminator (Nikko Materials' CVP700 two-stage laminator), resin sheets with the protective film removed were laminated onto a single side of a 12-inch silicon wafer (775 μm thick). This lamination was performed by bonding the resin composition layer to the silicon wafer. The support of the resin sheet was peeled off, exposing the resin composition layer. The exposed resin composition layer was then further laminated with the same method, removing the support, forming two resin composition layers (total thickness 100 μm) on a single side of the 12-inch silicon wafer. It should be noted that the lamination was performed by depressurizing for 30 seconds to bring the pressure below 13 hPa, followed by pressing at 100°C and 0.74 MPa for 30 seconds.
[0250] Next, the silicon wafer with the resin composition layer is heated in an oven at 100°C for 30 minutes, and then further heated at 200°C for 90 minutes. The resin composition layer is cured by this heating to obtain a sample laminate X with a "silicon wafer / cured layer" structure.
[0251] The warpage of the obtained sample laminate X was determined using a Thermoire AXP apparatus (Akorometrix). The measurement was performed in accordance with JEITA EDX-7311-24, a standard of the Electronic Information Technology Industries Association.
[0252] Specifically, an imaginary plane, derived using the least squares method from all data of the evaluation substrate surface (the side of the cured layer opposite to the silicon wafer) in the measurement area, is used as a reference plane. The difference between the minimum and maximum vertical height from this reference plane to the evaluation substrate surface is calculated as the warpage amount. The measured warpage amount is evaluated according to the following criteria: a smaller warpage amount indicates more effective warpage suppression.
[0253] [Evaluation Criteria for Warpage] “○”: Warpage is greater than 0 μm and less than 2,000 μm. “△”: Warpage greater than 2,000 μm and less than 2,500 μm. "×": Warpage is greater than 2,500 μm.
[0254] <Experimental Example 3: Evaluation Test of Reflow Solderability> (1) Substrate treatment of copper foil For the glossy surface of electrolytic copper foil (Mitsui Metals & Minerals Co., Ltd.'s "3EC-III", 35μm thick), a 1μm etching process was performed using an etchant (MEC's "CZ8101") to roughen the copper surface. Next, a rust inhibitor (MEC's "CL8300") was used to treat the roughened surface of the copper foil. Finally, the copper foil was heated in an oven at 130°C for 30 minutes to obtain CZ-treated copper foil.
[0255] (2) Preparation of inner layer substrate As the inner layer substrate, a glass cloth substrate epoxy resin double-sided copper-clad laminate (copper foil thickness 18μm, substrate thickness 0.4mm, Panasonic "R1515A") was prepared. The copper surface of this inner layer substrate was roughened by etching 1μm on both sides using an etchant (MEC "CZ8101"). Then, the inner layer substrate was subjected to a heat treatment at 130°C for 30 minutes.
[0256] (3) Lamination of resin composition layers The protective film is peeled off from the resin sheet to expose the resin composition layer. Using an intermittent vacuum pressure laminator (Nikko Materials, CVP700, two-stage lamination laminator), resin sheets are laminated on both sides of the inner layer substrate with the resin composition layer in contact with the inner layer substrate. The lamination is performed by adjusting the pressure to below 13 hPa after a 30-second depressurization, followed by pressing at 120°C and 0.74 MPa for 30 seconds. Next, a heat pressurization is performed at 100°C and 0.5 MPa for 60 seconds. Afterward, the support is peeled off to expose the resin composition layer.
[0257] (4) Lamination of copper foil and curing of resin composition layer Under the same conditions as described in "(3) Lamination of the resin composition layer", the treated surface of the CZ-treated copper foil is laminated onto the exposed resin composition layer. Furthermore, the resin composition layer is heat-cured at 200°C for 90 minutes to form an insulating layer as the cured product layer. Thus, an evaluation substrate Y having a layer structure of CZ-treated copper foil / insulating layer / inner substrate / insulating layer / CZ-treated copper foil is obtained.
[0258] (5) Evaluation test of reflow soldering resistance Evaluation substrate Y was cut into 100mm × 50mm pieces to obtain test pieces. The test pieces were subjected to 10 cycles of feeding into a reflow soldering apparatus (HAS-6116, manufactured by Antom Corporation, Japan) that reproduces a solder reflow temperature peak of 260℃ (reflow temperature profile based on IPC / JEDEC J-STD-020C). This test was performed on 5 test pieces. The test pieces were visually observed after the test, and their reflow resistance was evaluated according to the following criteria.
[0259] [Evaluation of reflow soldering resistance] “○”: In all the test pieces, the copper foil treated by CZ did not show any abnormalities such as expansion. “△”: In one test piece, the CZ-treated copper foil exhibited abnormalities such as expansion. "×": In more than two test pieces, the CZ-treated copper foil exhibited abnormalities such as expansion.
[0260] <Experimental Example 4: Appearance Evaluation of Resin Composition Layer> Before applying the protective film, visually inspect the resin composition layer on the resin sheet. Evaluate the appearance of the resin composition layer based on this visual inspection and according to the following criteria.
[0261] [Appearance evaluation of the resin composition layer] “○”: The resin composition layer is free of unevenness and pinholes. “△”: Unevenness or pinholes exist in part of the resin composition layer. "×": The resin composition layer is uneven or has pinholes.
[0262] [Table 1] .
Claims
1. A resin composition comprising: (A) A compound having a free radical polymerizable group at the end, a weight-average molecular weight (Mw) greater than 5,000 and less than 300,000, and a tensile modulus of elasticity of less than 1 GPa as determined by JIS K7161 at 25 °C; (B) Inorganic filler materials; and (C) Compounds with free radical polymerizable groups and a weight-average molecular weight (Mw) of less than 5,000.
2. The resin composition according to claim 1, wherein, (A) The ingredient contains an imide skeleton.
3. The resin composition according to claim 1, wherein, (A) The component contains an imide backbone in the main chain.
4. The resin composition according to claim 1, wherein, (A) The component comprises the structure shown in the following formula (A-1), [Chemistry 1] In equation (A-1), R A1 * indicates a tetravalent group obtained by removing the anhydride group from a tetracarboxylic dianhydride; * indicates a linking bond.
5. The resin composition according to claim 4, wherein, (A) The composition comprises the structure shown in formula (A-1) above and the structure shown in formula (A-3) below. [Chemistry 2] In equation (A-3), R A3 * indicates a divalent group obtained by removing two hydroxyl groups from a polyol compound having two or more hydroxyl groups in one molecule; * indicates a linking bond.
6. The resin composition according to claim 1, wherein, (B) The content of component is 50% or more of the non-volatile components of the resin composition by mass, which is 100% by mass.
7. The resin composition according to claim 1, wherein, (A) The component contains one or more structural units selected from polyolefin structural units, polycarbonate structural units, polyether structural units, polyester structural units, poly(meth)acrylic structural units and polysiloxane structural units.
8. The resin composition according to claim 1, wherein, (A) The component contains polyolefin structural units.
9. The resin composition according to claim 1, wherein, (C) The component contains maleimide-based free radical polymerizable compounds.
10. The resin composition according to claim 1, wherein, (A) The content of component is 0.1% by mass or more and 30% by mass or less relative to 100% by mass of non-volatile components in the resin composition.
11. The resin composition according to claim 1, wherein, (C) The content of component is 5% or more and 40% or less of the non-volatile components of the resin composition by mass relative to 100% of mass.
12. The resin composition according to claim 1, wherein, The mass ratio of component (A) to component (C) (content of component (A)) / (content of component (C)) is greater than 0.01 and less than 1.
5.
13. The resin composition according to claim 1, further comprising (D) a polymerization initiator.
14. The resin composition according to claim 1, further comprising (E) a polymeric resin.
15. The resin composition according to claim 1, used to form an insulating layer of a circuit board.
16. A cured product, which is a cured product of the resin composition according to any one of claims 1 to 15.
17. A resin sheet comprising a support and a layer of resin composition formed on the support, The resin composition layer comprises the resin composition according to any one of claims 1 to 15.
18. A circuit board comprising a cured product of the resin composition according to any one of claims 1 to 15.
19. A semiconductor device comprising the circuit board of claim 18.
Citation Information
Patent Citations
Silicone-containing polyimide resin, silicone-containing polyamic acid and their production
JP2000319386A
Polyimidesilicone resin, solution composition thereof, and polyimidesilicone resin coating film
JP2002012667A
Thermosetting resin composition containing modified polyimide resin
JP2006037083A
Resin composition for encapsulation, and semiconductor device based on the same
JP2018168217A
